Thermal expansion deformation of cementitious grout material during heating process - Ya Shen; Qingtao Li; Hangxu Zhao (European Journal of Environmental and Civil Engineering, 2026)

Introgression shapes the genomic conflict landscape of Malus, providing evidence for a reticulate backbone in a woody crop lineage - Xiao-Ya Li; Zhao-Qian Niu; Ya-Wen Zheng; Jue-Lin Huang; Dai-Kun Ma; Jia-Xin Huang; Qiang Hao; Ti-Cao Zhang; Si-Yu Xie; Chao Xu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2026)

Promoting the terminal zero-pollution goal of hydrogen fuel cell vehicles: A stochastic evolutionary game analysis - Dan Zhao; Ya Zhang; Ye-kai Li; He-ping Wang; Jin-huan Tang; Jian Wang (Fuel, 2026)

A random field-based methodology for offshore monopile design with soil spatial variability - Tao Zhao; Indrasenan Thusyanthan; Ya Li (Computers and Geotechnics, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Candosins A-L: potential antiparkinsonian agents from Candolleomyces sp. - Tong-De Zhao; Xue-Qiong Yang; Wei Chen; Hua Xu; Yan-Wei Yin; Yun-Li Zhao; Ya-Bin Yang; Zhong-Tao Ding (Phytochemistry, 2026)

Rainfall modulates the divergent responses of bacterial and fungal communities to naphthalene contamination in soil - Yuntao Zhao; Duo Zhang; Xin Wang; Yong Cui; Ying Guo; Wei Su; Chen Hong; Wenxin Li; Mengwan Lin; Yixiang Chen; Haobo Ya; Jiayu Chen; et al. (Applied Soil Ecology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Development of a NIR fluorescent probe HDI based on Zinc-mediated competitive coordination for multidimensional detection of glyphosate in complex systems - Ya-Tong Liu; Xi-Yue Luo; Bu-Xiao Wu; Yi-Wen Cui; Jun-Wen Wang; Ying-Kai Yuan; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

Addressing fruit allergen detection gaps: A validated LC-MS/MS method for eight allergenic fruits in foods - Yingnan Shencheng; Meizhen Zhou; Yumeng Zhao; Siyi Li; Yutong Xu; Yanan Gao; Xiaoxue Jia; Min Gao; Rong Zhang; Shuyan Liu; Feng Ye; Ya Zhang; et al. (Food Chemistry, 2026)

Integration of nontargeted screening with in vitro bioassays to evaluate and identify estrogenic compounds in food contact materials - Hongyan Li; Linhao Ying; Ya Chen; Wendi Fang; Yuxia Hu; Chao Deng; Lei Zhao; Jiangdong Zhang (Food Chemistry, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Gestational exposure to short-chain chlorinated paraffins induces sex-specific hepatic steatosis in adult mouse offspring - Xiaoke Wang; Jiayi Tang; Lingjuan Yang; Fangsicheng Zhang; Zhaoping Shen; Yilu Duan; Ying Li; Yufei Ge; Jie Li; Ya Zhang; Yuxin Li; Xinyuan Zhao (Chemico-Biological Interactions, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Revealing the anti-ferroptosis guanidine alkaloids from Buthus martensii Karsch via a NMR-guided isolation combined with in vitro, in silico, and network pharmacology - Wen-Kai Zhao; Tao-Li Hao; Ya-Zhou Kuang; Tong Sun; Hong-Bing Zhang; Yu-Ming Liu (Natural Product Research, 2026)

Fluorescence and SERS dual-mode sandwich lateral flow test strip utilizing concanavalin A modified trimetallic polydopamine with rhodamine B loaded UiO-66 immunoprobe for visual and sensitive detection of Escherichia coli - Wen-Bo Zhao; Xiao Liang; Zi-Tao Zhong; Liu Yuan; Ji-Tao Li; Qiu-Lan Li; Qin-Qin Han; Ya-Ling Yang (Food Bioscience, 2026)

Probiotic fermentation enhances the antihypertensive activity of Astragali radix via redox-inflammation-endothelial interaction axis - Yue-Yue Liu; Zhen-Hui Pan; Ya-Li Zhao; Teng-Gen Hu; Hong Wu (Food Bioscience, 2026)

Fabrication of a fluorescence/colorimetric multi-channel sensor array utilizing riboflavin derived bimetallic-doped Ce-MOF based peroxidase mimic for highly efficient determination of heavy metal ions - Xiao Liang; Qiu-Lan Li; Wen-Bo Zhao; Peng Yang; Ya-Ling Yang; Zi-Tao Zhong (Environmental Research, 2026)

Study on the mechanism of synergistic adsorption of CO2 and Hg0 by Mg-MOF-74-derived modified composites based on experiment and density functional theory - Peng Cheng; Li Jia; Jia-hao Zhao; Ya-wen Wu; Yue Yu; Xiao-fang Gao; Qing Meng; Yan Jin (Chemical Engineering Journal, 2026)

Red mud derived alkaline aggregates as wetland substrates for acidic wastewater purification - Shigui Zhao; Qing Wang; Qilong Li; Guanglei Wang; Ya-nan Luan; Chen Jiao; Changqing Liu; Yue Yin (Bioresource Technology Reports, 2026)

A dual-enzymatic activity/SERS dual-mode sensor array based on BSA-Cu nanoflowers for sensitive detection of various foodborne pathogens - Wen-Bo Zhao; Xiao Liang; Liu Yuan; Ji-Tao Li; Ya-Ling Yang; Zi-Tao Zhong (Analytica Chimica Acta, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Nonlinear coupling of low-frequency hull heave and high-frequency skirt bounce in an air-cushion vehicle - Ya Zhong; Peng Xiao; Zhiqun Guo; Qingyan Zhao; Haolan Lu; Zhenglin Li (Ocean Engineering, 2026)

Physiological, transcriptomic, and metabolomic insights into the sugar stress tolerance mechanisms of Clavispora lusitaniae and its fermentation potential - Ya Zhang; Siyi Liu; Runshen Zhao; Fanghang Qiu; Meiyue Han; Qiumei Zhang; Xingquan Han; Xucheng Zhu; Akhtiar Ali; Weiwei Li; Xiuting Li; Baoguo Sun (International Journal of Food Microbiology, 2026)

Nano-assembly of dioscin via zein–Angelica sinensis polysaccharide composite nanocarriers: structure, stability, bioaccessibility and bioactivity - Tian-Le Mao; Yue Wu; Zhi-Xin Xu; Fan Yang; Jing Li; Xin Guo; Qian-Lan Wu; Ya-Fang Shang; Kiran Thakur; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

CRISPR-Cas12a-coupled split-promoter activator bridge enables reusable one-reporter-multiple-target cell-free nucleic acid diagnostics - Fengling Fang; Mingming Zhao; Weiquan You; Xiangjun Tang; Shanjian Chen; Yao Yin; Qishui Ou; Yueguo Li; Ya Fu (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Unraveling the molecular evolution and immune functions of Lr-CD40 in Lethenteron reissneri - Liang Zhao; Zihao Yan; Mingwei Du; Xiaoping Song; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Feng Sun; Yinglun Han (Fish Physiology and Biochemistry, 2026)

Three new naphthoquinone-based meroterpenoids from Streptomyces sp. HBERC-16614 with antibacterial activities - Ya-Ni Zhang; Man-Li Liu; Fang Liu; Zhi-Gang Zhang; Zhao-Yuan Wu; Li-Qiao Shi; Zhong-Yi Wan; Yue-Ying Wang; Fei Zhang; Kai-Mei Wang; Wei Fang (Natural Product Research, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Machine learning-driven 3D architecture of mineralized dolomite and potential rare earth element resources at Bayan Obo - Guoqiang Xue; Pengfei Lv; Qingyun Di; Jian Wang; Weiying Chen; Xin Wu; Ji’en Zhang; Ya Xu; Yonggang Zhao; Xianhua Li (Science Bulletin, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Target-oriented molecularly imprinted polymers enable rapid ambient ionization mass spectrometric analysis of trace tetrachlorobisphenol a in environmental samples - Ya Jiao; Shuo Gao; Xiaoxuan Han; Yong Tian; Xiaoxu Huo; Jianwei Zhao; Xiaofeng Dong; Chunguang Liu; Weiliang Wang; Guifen Zhu; Xuwei Chen; Ming-Li Chen (Journal of Hazardous Materials, 2026)

Evaluation of a virtually screened quorum sensing inhibitor for Morganella psychrotolerans as a preservative in yellowfin tuna fillets - Di Wang; Yazhe Wang; Ya Wei; Zhenhua Ma; Pengxiang Yuan; Gang Yu; Chunsheng Li; Yongqiang Zhao (Food Chemistry, 2026)

Recent advances in polysaccharide extraction: Mechanisms, hybrid strategies, and emerging technologies - Ya Zhao; Fei Wang; Yaxing Zhang; Liangxiao Zhang; Xiao Wang; Peiwu Li (Carbohydrate Polymers, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Microglial tunneling nanotubes: an intercellular transfer facilitating mitochondrial dysfunction and neuroinflammation in experimental cerebral malaria - Yan Shen; Yi Wang; Chao Yang; Jun Wang; Yuxiao Huang; Qinghao Zhu; Ganze Li; Tong Li; Jiayi Sun; Jie Ren; Xiaolin Chen; Shuhan Xing; et al. (Apoptosis, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

Significant Mg isotope disequilibrium during crustal anatexis: Implications for heterogeneous Mg isotopic compositions in the continental crust - Er-Lin Zhu; Qiong-Xia Xia; Zhao-Ya Li; Hao-Hong Shu (Geochimica et Cosmochimica Acta, 2026)

Structure-guided discovery of neutralizing epitopes enables rational design of a multi-epitope nanoparticle vaccine against SVCV - Yu-Ya Li; Liang Zhao; Xue-Feng Wei; Xiao-Hang Ren; Jun-Yao Xia; Zhao Zhao; Bin Zhu (Fish & Shellfish Immunology, 2026)

Environmental heat and cold stress, thyrotropin abnormalities, and reduced fecundability in 14 million Chinese couples: A nationwide preconception cohort study - Xinghou He; Mengyao Li; Ying Yang; Xinyi Lv; Hongbing Xu; Bin Zhang; Long Wang; Chuanyu Zhao; Jiahui Liu; Yuan He; Jianbing Wu; Xinghua He; et al. (Environmental Research, 2026)

Assessing the NO and SO2 pollution impacts on the Δ3-carene photooxidation mechanisms - Ya Zhao; Chong Wang; Yufeng Shao; Yingqi Zhao; Yifei She; Hua Xie; Jiayue Yang; Weiqing Zhang; Gang Li; Ling Jiang; Xueming Yang (Environmental Pollution, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Formal synthesis of (-)-warburganal and synthesis of (+)-isodrimenin - Xian-Hui Zhao; Liang Zhao; Yue-Cheng Wu; Ya-Jing Bian; Hui-Jing Li; Yan-Chao Wu (Natural Product Research, 2026)

Oxime ester–linked N-phenylphthalimide derivatives as PPO inhibitors: structure–activity relationships, herbicidal activity, crop selectivity, and in silico safety assessment - Xian-Ming Zhang; Yue-Li Zou; Ya Jiang; Si-Yi Yao; Shuang Gao; Li-Xia Zhao; Yu-Long Liu; Ying Fu (Pesticide Biochemistry and Physiology, 2026)

Genetic diversity analysis of three geographical populations of Triplophysa yarkandensis macroptera in arid northwestern China - Ya Liu; Hangyu Lin; Hongyu Ke; Han Zhao; Zhongmeng Zhao; Shengqi Su; Qiang Li (Journal of Arid Environments, 2026)

4D-LysM functionalized optical fiber SPR sensor for selective detection of Pseudomonas aeruginosa - Wanlu Zheng; Weixin Kong; Po Jin; Zhong Li; Yong Zhao; Ya-nan Zhang; Yongqiang Fan; Dake Xu (Chemical Engineering Journal, 2026)

Optimization of Dynamic-Staged Drought-Resistance Operation Strategy for Reservoirs - Jie Li; Zhao Liu; Qin-nan Mao; Jin-xia Zhang; Ya-jian Wei; Si-qi Shen (Water Resources Management, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

A new paradigm for electrical modeling in site leakage diagnostics: A label-scarce three-dimensional simulation surrogate using physics-informed neural networks - Feng Chen; Aixia Zhou; Linhai Ye; Wenchang Li; Xiaochen Sun; Jie Zhang; Youcai Zhao; Qifei Huang; Ya Xu (Water Research, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Three new pregnane alkaloids from Sarcococca hookeriana - Li-xia Zhang; Xiao-hui Sun; Gang Ke; Fang-you Chen; Ya-mei Zhang; Pu-zhao Zhang (Phytochemistry Letters, 2026)

Sparteine-type alkaloids with anti-tomato spotted wilt virus from the seeds of Lupinus angustifolius L. - Jian-Guo Tan; Cheng-Feng Liu; Li Wang; Xing-Ya Wu; Li-Hua Zhao; Xiao-Jiang Hao; Zhan-Xing Hu (Pesticide Biochemistry and Physiology, 2026)

Metamifop-induced human breast cancer cells proliferation: Revealing a proliferation mechanism distinct from 17β-estradiol - Jingjing Wu; Ya Zhou; Yu Wang; Junqi Zhu; Lu Lin; Huihua Tan; Shiling Liu; Yahui Li; Feng Zhao (Pesticide Biochemistry and Physiology, 2026)

Fluid - flexible skirts interaction during air leakage of an air-cushion vehicle on water surface - Ya Zhong; Zhiqun Guo; Haolan Lu; Qingyan Zhao; Zhenglin Li (Ocean Engineering, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Pressure-driven flavor formation in rapeseed oil: an integrated multi-omics approach - Yini Yang; Chang Zheng; Ran Zhao; Ya Xu; Lanhang Yao; Wenlin Li; Changsheng Liu; Chuyun Wan; Qi Zhou (Food Chemistry, 2026)

Tropomyosin-targeted LC-MS/MS for quantitative detection of molluscan allergens in foods: Method validation and application - Yumeng Zhao; Peijie Yang; Yingnan Shencheng; Siyi Li; Meizhen Zhou; Min Gao; Feng Ye; Rong Zhang; Ya Zhang; Yi Li; Shupeng Yang (Food Chemistry, 2026)

W1/O/W2 emulsion gels stabilized by genipin-crosslinked chitosan/protein conjugates: Unveiling the impact of protein structure on their hierarchical microstructure, rheology, and controlled release of phycocyanin and astaxanthin - Jiao Yu; Ya Zhao; Li Li; Mohammad Molaveisi; Qilong Shi (Food Chemistry, 2026)

Evaluating microphysics scheme impacts on summer precipitation in Northwestern China using a convection permitting WRF model - Ya Huang; Qingyun Duan; Yong Zhao; Lihua Chen; Yanping Li (Atmospheric Research, 2026)

Fine mapping and candidate gene dissection of the wheat powdery mildew resistance gene PmPBDH - Yuli Jin; Jiatong Li; Delin Li; Ningning Yu; Ya Zhao; Bo Wang; Jun Guo; Jiadong Zhang; Guantong Pan; Yaoxue Li; Yintao Dai; Nina Sun; et al. (Theoretical and Applied Genetics, 2026)

Harpin Protein Treatment Makes a Positive Impact on Maintaining the Postharvest Quality of Strawberry Fruits - Hao Li; Zihang Ouyang; MuSha She; ManTong Zhao; CaiXia He; Haoru Tang; Ya Luo (Journal of Plant Growth Regulation, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Visco-elastic interface and dynamic response of a lined tunnel in anisotropic rock mass under unloading waves - Xue-Qian Fang; Zhao-Feng Zhong; Bai-Lin Li; Xin-Yu Liu; Ya-Wen Xiong (Soil Dynamics and Earthquake Engineering, 2026)

An extended vector inclination method for inferring detailed slip surfaces beneath landslides from SAR and optical satellite remote sensing image - Ya Kang; Zhong Lu; Chaoying Zhao; Yufen Niu; Liquan Chen; Wei Qu; Menghua Li (Remote Sensing of Environment, 2026)

Photooxidation and ozonolysis of α-pinene and limonene mixtures: Mechanisms of secondary organic aerosol formation and cross-dimerization - Yingqi Zhao; Ya Zhao; Chong Wang; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2026)

Ursolic acid nanoemulsion system for inhibition of goji berry black mold caused by Alternaria alternata - Liang Liu; Huaiyu Zhang; Junjie Wang; Yueli Zhou; Dayuan Chen; Ya Yang; Jing Li; Haotian Ma; Zhao-Jun Wei (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

AID/APOBEC-like cytidine deaminases are important mediators of VLR-based adaptive immunity in lampreys - Zihao Yan; Jingjing Lu; Yuesi Zhou; Liang Zhao; Ding Li; Huining Jia; Ayqeqan Nurmamat; Min Xiu; Shuyuan Zhang; Ruyu Zhuang; Ya Pang; Tiesong Li; et al. (Fish & Shellfish Immunology, 2026)

Dihydromyricetin-loaded nanocochleates with a distinctive cylindrical structure: Effects of varying calcium chloride (CaCl2) concentrations on the stability and controlled release of dihydromyricetin - Mohammad Molaveisi; Ya Zhao; Li Li; Qilong Shi (Food and Bioproducts Processing, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Chitosan/ZIF-8 composite ultralight foam for efficient removal of NSAIDs and multiple dyes: Bridging collaborative adsorption and multidimensional mechanistic insights - Yan-Shu Xiong; Lu-Nan Zhao; Wen Li; Xian-Yan Tao; Shu-Ya Du; Fangxue Hang; Caifeng Xie; Kai Li (Carbohydrate Polymers, 2026)

Enterococcus Durans J396 Isolated from the Intestine of a Pig Enhances the Antioxidant Activity in Caenorhabditis Elegans - Juntong Yu; Ruyi Gao; Zhuoming Sun; Wenyu Li; Dongyu Zhao; Tianxu Pan; Jialin Guo; Tongxuan Zhang; Shuyuan Yu; Haibin Huang; Nan Wang; Chunwei Shi; et al. (Probiotics and Antimicrobial Proteins, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

The Classification History of Lamiaceae and a Generic Synopsis in China - Si-Cheng Xu; Su Liu; Ya-Ping Chen; Yue Zhao; Fei Zhao; Chun-Lei Xiang; Bo Li (The Botanical Review, 2026)

Evaluation of synthetic peptide vaccines based on phage display technology for grass carp reovirus - Zhu-Yang Deng; Yu-Ya Li; Yong-Qi Liu; Le-Yang Chen; Zhao Zhao; Bin Zhu (Aquaculture, 2026)

Diffusion dynamics coupled with in situ etching enable controlled growth of InAs quantum dots with narrow SWIR emission - Feng Zhao; Hong-Wei Duan; Ye Wang; Zong-Shuo Liu; Zhou Li; Sanxia Yin; Shulin Chen; Ya-Kun Wang; Liang-Sheng Liao (Science Bulletin, 2026)

Bidirectional regulation strategies of food microorganisms based on mechanistic insights into temperature, osmotic, and acid stresses - Ya Zhang; Fanghang Qiu; Weiwei Li; Runshen Zhao; Xiuting Li; Baoguo Sun (Food Research International, 2026)

Cloning, tissue distribution, and stimulus-responsive mRNA expression of CD10 (neprilysin) in Lethenteron reissneri - Liang Zhao; Zihao Yan; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Mingwei Du; Feng Sun; Yinglun Han (Fish & Shellfish Immunology, 2026)

U-shaped association between outdoor artificial light at night exposure and metabolic syndrome in Chinese youth: Findings from a nationally representative study - Wen-xin Ge; Zhao-huan Gui; Zhi-Yong Zou; Li-qing Yao; Wen-wen Bao; Le-bing Wang; Li-xin Hu; Zheng-ge Jin; Wan-xin Wu; Jun Ma; Ying-Hua Ma; Ya-jun Chen (Environmental Pollution, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

DNA tetrahedron-supported DNA walker for subtype-specific analysis of extracellular vesicles - Jingjing Xu; Zhikai Fang; Kai Ni; Lijuan Li; Ya Cao; Hongwei Yang; Jing Zhao (Chemical Engineering Journal, 2026)

A structurally distinct arabinose-bridged arabinogalactan from Lycium barbarum as a TLR4-activating adjuvant for nanovaccine-based cancer immunotherapy - Chun-Jie Bao; Meng-Qiu Liu; Ya-Nan Liu; Li-Qiang Zhao; Yu-Xuan Li; Xin-Lan Zhang; Fang Zhang; Sheng Guo; Er-Xin Shang; Jia-Lun Duan; Jin-Ao Duan (Carbohydrate Polymers, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Dual-functional fluorescent bio-sensor for detecting ONOO− and polarity for targeted-diagnosis of NAFLD in vivo fluorescence imaging - Ya-Tong Liu; Yue-Li Zou; Yu-Yang Wang; Xi-Yue Luo; Si-Yi Yao; Jing-Yi Li; Zhiyong Xing; Li-Xia Zhao (Analytica Chimica Acta, 2026)

Isolation and antibacterial activity of three new flavonol compounds from Sophora flavescens - Si-Han Wang; Xiang-Yu Zhao; Zhi-Kang Chen; Yun Gao; Xin-Min Li; Ya-Juan Gao; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Coupling iron oxide with iron single-atom catalyst promotes neutral electrochemical nitrate reduction from water - Jinshan Wei; Xihui Lu; Hexing Lin; Shao-Qing Liu; Xiaoxiao Wei; Meng Sun; Gang Liu; Chengzhi Hu; Liangjie Wang; Huazhang Zhao; Ya-yun Li (Water Research, 2026)

Co-delivery of phycocyanin and astaxanthin using nanocochleates as a novel delivery vehicle: Effects of pigment concentration on physicochemical, structural, and in vitro digestion properties - Mohammad Molaveisi; Ya Zhao; Li Li; Qilong Shi (Journal of Food Engineering, 2026)

Z-scheme Ti-BPDC-Ru/WO3 heterojunction for selective methane-to-methanol photoconversion - Ya-Ting Zheng; Ya-Nan Wang; Lu Feng; Ye Wang; Tian-Lei Sun; Wen-Wen Dong; Jun Zhao; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Butyrate-Producing Mixed Probiotics Alleviate MRSA-Induced Acute Lung Injury in Mice by Promoting M2 Macrophage Polarization - Minghan Li; Tianxu Pan; Juntong Yu; Xueting Wang; Ruyi Gao; Ya Wang; Dongyu Zhao; Xinyi Zhou; Hongye Li; Jialin Guo; Nan Wang; Haibin Huang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Healthy diet and slower biological aging as protective factors against microvascular complications in type 2 diabetes - Han Zhou; Shuai Ben; Qian Ma; RuiKang Yang; Jiao Xia; XiongYi Yang; Jing Li; JunYa Zhu; Qian Liu; Ya Zhao; Na Li; Kun Liu; et al. (GeroScience, 2025)

Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Effects of soil porosity on water stability of aggregates - Hairu Li; Gang Liu; Chenxi Dan; Zongjiang Zhou; Ya Liu; Chang Liu; Enshuai Shen; Qiong Zhang; Xiaolin Xia; Dandan Liu; Zhen Guo; Xining Zhao (Soil and Tillage Research, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Triphenylamine-based fluorescent probes for lipid droplet detection and non-alcoholic fatty liver disease identification - Jing-Yi Li; Ya-Tong Liu; Zhi-Bo Jiang; Si-Yi Yao; Fan-Qi Shen; Yu-Yang Wang; Yue-Li Zou; Li-Xia Zhao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Resilient polyurea barriers for copper smelting wastewater containment: Synergistic effects of microstructural optimization and heavy metal immobilization - Feng Chen; Linhai Ye; Wenchang Li; Rui Xiang; Youcai Zhao; Qifei Huang; Ya Xu (Journal of Cleaner Production, 2025)

Comparative studies of the NOx impacts on the photooxidation mechanisms of isomeric monoterpenes of β-pinene and limonene - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2025)

Study on the effects of representative spice polyphenols on the in vitro digestive properties of tilapia myofibrillar protein and its mechanism of action: based on physical and chemical properties and enzyme activity - Zirui Fu; Jun Li; Ya Wei; Jianwei Cen; Huan Xiang; Xiao Hu; Chunsheng Li; Yanyan Wu; Shengjun Chen; Yongqiang Zhao; Hui Huang; Shuxian Hao (Food Chemistry, 2025)

Emerging adsorbent systems for sugar-derived contaminants removal: Sustainable strategies for sugar processing wastewater remediation - Yan-Shu Xiong; Lu-Nan Zhao; Shu-Ya Du; Xian-Yan Tao; Yan-Hong Wei; Hai-Qin Lu; Wen Li; Kai Li; Hao Dong (Food Chemistry, 2025)

Proteomic insights into DEM-induced oxidative stress: Glycolytic and antioxidant synergy in beef colour stability - Cai-Yun Li; Wen-Jun Zhao; Ya-Ning Qu; Yu-Bin Zhang (Food Chemistry, 2025)

Non-optimum temperature exposure may impair cardiac structure and function: A repeated-measure analysis based on echocardiography - Xingyi Qiu; Yufei Cheng; Qinglin He; Ya Gao; Wenshu Li; Xiaowei Xue; Mengyuan Cheng; Renjie Chen; Gang Zhao; Xianhong Shu (Environmental Research, 2025)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

Research on position self-detection technology of pneumatic actuator with dual-electrode sensing - Tenghong Su; Xiao Lei; Xinjie Zhao; Jianping Li; Yili Hu; Jijie Ma; Ya Li; Yingting Wang; Jianming Wen (Chemical Engineering Journal, 2025)

Reversibility of the reproductive toxicity induced by hexafluoropropylene oxide trimer acid (HFPO-TA) in adult zebrafish (Danio rerio) - Dan Yang; Xuan Ren; Xiaohui Zhao; Shasha Dong; Xiaoying Li; Yawei Shi; Ya Sun; Guanghui Ding (Aquatic Toxicology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Exploring the evolutionary conservation and functional implications of Endothelin Converting Enzyme 1 (ECE1) in lamprey (Lethenteron reissneri) - Shuyuan Zhang; Zihao Yan; Ayqeqan Nurmamat; Ruyu Zhuang; Yuesi Zhou; Min Xiu; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2025)

Bicyclol improves cognition deficits and inhibits oxidative stress-induced neuronal cell apoptosis in alzheimer’s disease via Nrf2/HO-1 pathway - Shuyue Li; Ya Gao; Xiangjian Zhang; Jiadong Lang; Xiang Liu; Yidan Zhang; Jian Zhang; Yuan Zhao; Cui Chang; Xuan Gao; Jin Zhou; Donghua Yu; et al. (Metabolic Brain Disease, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Mitochondrial dysfunction-associated cellular senescence is partially involved in bleomycin-induced pulmonary fibrosis in mice - Ya-Xin Yao; Xue Lu; Zhao Li; Hao-Yu Liao; Zhi-Bing Liu; Hui Zhao; Hua Wang; De-Xiang Xu; Zhu-Xia Tan (Toxicology and Applied Pharmacology, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Advanced strategies in organoid/organ-on-a-chip for food safety and nutrition - Yiyan Zhou; Feiran Wang; Rui Zhao; Tianyi Huang; Wentao Su; Ya Wen; Zhixian He; Dong Li (Food Research International, 2025)

Evolutionary conservation and Immunoregulatory function of LOXL3 gene in lamprey - Ya Pang; Zihao Yan; Yicheng Gao; Ding Li; Liang Zhao; Guoxiu Ma; Yuetong Zhao; Mingwei Du; Feng Sun; Yinglun Han (Fish & Shellfish Immunology, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

Differential effects of size-specific PM components on stroke hospitalization in Northwest China's arid area - Huanhuan Wei; Ce Liu; Ya Xiao; Li He; Hao Zhao; Zhaoru Yang; Huan Chen; Ququmo Guoji; Bin Luo (Atmospheric Environment, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Picroside II Alleviates the Progression of Alzheimer’s Disease via the NLRP3/Caspase-1/GSDMD Pathway - Shuyue Li; Ya Gao; Yidan Zhang; Jian Zhang; Yuan Zhao; Cui Chang; Xuan Gao; Jungang Zhang; Guofeng Yang (NeuroMolecular Medicine, 2025)

Comparative transcriptomics unveils nitric oxide delaying leaf senescence in Chinese flowering cabbage by enhancing BrGATA21-mediated ROS scavenging - Zhen-liang Mou; Ze-xiang Zeng; Zong-li Liu; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ya-ting Zhao (Postharvest Biology and Technology, 2025)

Biodegradable and non-biodegradable microplastics affect greenhouse gas emissions through chemical diversity and microbial biodiversity - Ying Guo; Yajuan Tang; Yi Xing; Chen Hong; Wei Su; Wei Wen; Haobo Ya; Jiayu Chen; Han Zhang; Duo Zhang; Wenxin Li; Yixiang Chen; et al. (Journal of Hazardous Materials, 2025)

Efficient degradation of dichloromethane by novel cell-immobilized-filled biotrickling filters: Performance and mechanisms - Yaxue He; Xiaoyan Li; Rui Han; Aohan Zhang; Ya Deng; Piet N.L. Lens; Christian Kennes; Zhao Huang; Jianmeng Chen; Guangfeng Yang; Dongzhi Chen (Journal of Hazardous Materials, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

GSDME-dependent astrocyte pyroptosis promotes the progression of neuroinflammation in experimental cerebral malaria - Jun Wang; Qinghao Zhu; Guodong Tong; Kangjie Yu; Jiao Liang; Yuxiao Huang; Yi Wang; Chao Yang; Tong Li; Weilu Liang; Ganze Li; Xiaoran Liu; et al. (Apoptosis, 2025)

Extensive Introgression Failed to Erode Species Boundaries Among Multiple Sympatric Closely Related Species of Roscoea - Hong‐Fan Chen; Ryan Andrew Folk; Ya‐Li Wang; Wen‐Jing Wang; Guo‐Jun Shao; Mei‐Yuan Huang; Xiang‐Qin Yu; Li Li; Jian‐Li Zhao (Molecular Ecology, 2025)
How species boundaries are maintained among sympatric closely related species experiencing gene flow is a puzzling question in evolutionary biology. Although introgression is commonly documented, the dynamics and gene function of introgression have rarely been explored to probe why frequent introgression does not necessarily destroy species boundaries in sympatry. In this study, we employ whole‐genome resequencing data to examine introgression among five closely related species of Roscoea that coexist in a ‘sky island’ with seventeen distinct morphological traits. Our findings reveal that introgression has led to the phylogenomic discordance between nuclear and chloroplast genomes among these morphologically distinct species. Additionally, introgression is predominantly asymmetrical in both intensity and gene function, particularly concerning recombination. Notably, the majority of gene functions associated with introgressed loci are unrelated to reproductive processes. Our results suggest that closely related species with incomplete allele assortment can coexist despite theoretical predictions, highlighting the semipermeable nature of species boundaries as reproductive isolation develops. This provides a critical conceptual framework for understanding the interplay between introgression and species persistence. Our finding offers insights into how related sympatric species boundaries can be maintained in the face of frequent asymmetrical gene introgression.

Aporphine alkaloids and flavonoids from the roots of Fissistigma retusum (H. Lév.) Rehder - Ya-Ting Xiao; Xue-Na Zhao; Han Li; Ying Ren; Yu-Hang Liu; Yu-Ming Liu (Natural Product Research, 2025)

Morphology, proteome and metabolome characterization of the sporoplasm of Ameson portunus (Microsporidia) - Ya-Li Xu; Min Zhou; Zhi-Qiang Zhu; Zhao-Zhe Xin; Jin-Yong Zhang (Journal of Invertebrate Pathology, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Comprehensive understanding long-term heavy metals release characteristics and environmental impacts of ultra-alkaline fly ash based roadbed materials - Shu Li; Ya Xu; Rongbin Xu; Yuxin Zhao; Zewei Liu (Journal of Hazardous Materials, 2025)

Heavy metals contamination in water-sediment systems of a large drinking water reservoir in southern China: Large-scale assessment and risk-based management - Yiping Li; Ya Zhu; Yu Chen; Can Wang; Guoli Zhao; Haiping Pan; Chuer Wang; Hangtong Bao; Muhammad Ibrahim; Eyram Norgbey (Journal of Cleaner Production, 2025)

Adsorption and coarsening of gold nanoparticles in iron (oxyhydr)oxides lead to high-grade gold mineralization - Feng-Xia Huang; Ya-Fei Wu; Katy Evans; Anthony E. Williams-Jones; Xin-Fu Zhao; Yong Wei; Wei Feng; Jian-Wei Li (Geochimica et Cosmochimica Acta, 2025)

Sustainable extraction of Lycium barbarum leaf Phenolics using deep eutectic solvents: Optimization, bioactivity, and functional food potential - Yi-Long Ma; Qian-Lan Wu; Lu Jian; Xin Guo; Jing Li; Tian-Le Mao; Zhi Li; Ya-Fang Shang; Kiran Thakur; Shao-Hua Yang; Zhao-Jun Wei (Food Chemistry, 2025)

Multilamellar nanocochleates as novel co-encapsulation systems for enhancement of the physicochemical properties and controlled release of astaxanthin and phycocyanin - Mohammad Molaveisi; Li Li; Ya Zhao; Qilong Shi (Food Chemistry, 2025)

Quality changes and deterioration mechanisms during frozen storage of starching tilapia fillets based on quality characteristics, protein properties and microstructure analysis - Qingqing Wu; Huan Xiang; Shuxian Hao; Jianwei Cen; Shengjun Chen; Yongqiang Zhao; Chunsheng Li; Hui Huang; Ya Wei (Food Chemistry, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Anthropogenic effects on Δ3-carene photooxidation: Different oxidants induce significant changes of secondary organic aerosol formation mechanisms - Ya Zhao; Chong Wang; Yingqi Zhao; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2025)

A NIR Isophorone-based Zinc Coordination Fluorescence Probe for the Detection of Glyphosate and Application in Environment, Food and Living Systems - Si-Yi Yao; Han-Wen Cui; Zhi-Bo Jiang; Hao Wang; Jing-Yi Li; Yu-Yang Wang; Fan-Qi Shen; Li-Xia Zhao; Ya-Tong Liu; Yue-Li Zou (Journal of Fluorescence, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Spatiotemporal distribution of neonicotinoids in urban rivers: implications for rainfall-driven pollution in Guangzhou, China - Ya-Ya Cai; Nan Li; Qian-Qian Zhang; Yue-Hong Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2025)

Andrograpalides A–N, structurally diverse ent-labdane diterpenoids with anti-inflammatory activities from the leaves of Andrographis paniculata - Xiao Zhang; Yan-Zhen Li; Ya-Ting Lai; Wei Zeng; Min Yu; Jun-Tao Huang; Hong-Lei Jin; Wei-Qun Yang; Zhong-Xiang Zhao (Phytochemistry, 2025)

Hydrodynamic and geomorphological responses of tidal flats to extreme climate events - Renzhi Li; Ya Ping Wang; Rui Yuan; Ning Zhao; Bixuan Tang; Zhixuan Feng; Bruno Castelle (Journal of Hydrology, 2025)

Public risk perception and treatment preferences for marine microplastic pollution: Choice experiments and the latent class model - Ya-Nan Zhao; Jing-Mei Li (Journal for Nature Conservation, 2025)

Preservation processes of liquid nitrogen spray freezing technology on Sebastes schlegelii in two stages of freezing and frozen storage: Focusing on changes in water status, protein characterization, texture properties and volatile compounds - Weijia Zhang; Zhuyu Yang; Wenjing Zhao; Lianfa Gong; Wentao Liu; He Xu; Lili Sun; Tingwei Zhang; Ya Li; Guiping Wang; Xinxing Xu; Yuanhui Zhao (Food Chemistry, 2025)

Key role of macrophyte-dominated habitats over cyanobacteria-dominated habitats in stability of microbial sulfur cycling in freshwater lakes - Rui-Ze Li; Zhi-Jie Zhu; Xing-Hao Li; Yi-Ying Jiao; Li-Ya Zhao; Zhao-Hua Li; Mo Chen (Environmental Research, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Insights into the synergistic effects of exogenous glycine betaine on the multiphase metabolism of oxyfluorfen in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Xu Zhen Shi; Ya Nan Qu; Si Ying Li; Gan Ai; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xuesheng Li; Yan Hui Wang (Journal of Hazardous Materials, 2025)

Two-step cascade degradation of Dongming lignite over Mo/N co-doped ZIF-67-based Co-Mo15@NC - Guang-Hui Liu; Hao-Dong An; Han Wang; Ya-Jun Ma; Yan-Jun Li; Yu-Hong Kang; Jie Kang; Wei Zhao; Sheng-Kang Wang; Xian-Yong Wei (Fuel, 2025)

Dual-response fluorescent triphenylamine chemoprobe HN2 for the detection of Cu2+ ions and H2S: Applications in real samples and biological imaging - Ya-Tong Liu; Qian-Qian Zhang; Jing-Yi Li; Guang-Yi Kuang; Si-Yi Yao; Hao Wang; Yue-Li Zou; Li-Xia Zhao (Food Chemistry, 2025)

Cyclic trace enzymatic hydrolysis pretreatment enhances brown rice: Cooking and taste - Yuanyuan Deng; Pengfei Zhou; Ya Li; Ping Li; Zhihao Zhao; Jiajia Wang; Lihuang Zhong; Guang Liu; Mingwei Zhang; Dong Liu; Jiarui Zeng (Food Chemistry, 2025)

Effects of mono- and di-glycerides/phospholipids (MDG/PL) on the bioavailability of lutein and DHA in rats: more effective for lutein - Shu-zhen Huang; Huan-huan Yin; Fang Tian; Liang Wang; Wen-jing Wu; Xiang Li; Yanrong Zhao; Xiao-ya Wang; Yun Li; Megan Terp; Ying-yi Mao; Jin-yao Chen (Food Bioscience, 2025)

Clinical characteristics and co-infection analysis of influenza a virus in pediatric respiratory infections: a study based on tNGS technology - Chunyun Fu; Qiang Huang; Jiangyang Zhao; Lishai Mo; Wenting Tang; Junming Lu; Yili Zhang; Xiangjun Lu; Ya Huang; Yanhua Feng; Xuehua Hu; Yanqing Tang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Rational design of vitamin B3 derived bimetallic doped Cu-MOF with laccase-like activity for the colorimetric detection of Cr3+ - Xiao Liang; Qiu-Lan Li; Wen-Bo Zhao; De-Zhi Yang; Ya-Ling Yang; Zi-Tao Zhong (Journal of Environmental Chemical Engineering, 2025)

From laboratory-level construction to pilot-level validation: Utilization of compound mutagenic bacterial agent for efficient treatment of kitchen waste - Zeyuan Wang; Ya Chen; Yu Hong; Lihua Li; Yuewen Zhang; Cheng Wang; Min Zhang; You Huang; Yani Huang; Mengna Zhao (Journal of Environmental Chemical Engineering, 2025)

A NIR sensitive fluorescence assay for the detection of glyphosate: HMB-Zn2+ system applied in environment, food and live mice - Ya-Tong Liu; Yue Hou; Jing-Yi Li; Guang-Yi Kuang; Si-Yi Yao; Hao Wang; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2025)

Heavy metal leaching and landfill gas emissions from a recirculated MSW landfill mixed with stabilized MSW incineration fly ash: Behavior and interactive effects - Yuan Gao; Weihua Li; Fanqi Du; Xue Li; Yingjie Sun; Changxia Zhao; Yingda Chen; Mingke Fan; Rongxing Bian; Weijie Gao; Huawei Wang; Ya-nan Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Simulation research on the effect of magnetic field uniformity on a single-stage adiabatic demagnetization refrigerator - Zhuo Chen; Jun Shen; Ya'nan Zhao; Wenshuai Zheng; Zhenxing Li; Jun Liu; Long Yang; Yian Lu (International Journal of Refrigeration, 2025)

Phycocyanin-butterfly pea (Clitoria ternatea L.) anthocyanin nanoparticles as novel high internal phase Pickering emulsion stabilizers with antioxidant and UV shielding properties - Jiao Yu; Ya Zhao; Li Li; Mohammad Molaveisi; Qilong Shi (Food Research International, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Screening and identification of two repellent active volatiles to Hyphantria cunea - Jin-Yan Lv; Zhao-Jun Meng; Ya-Nan Deng; Yan-Yan Li; Xin-Su Li; Shan-Chun Yan (Journal of Pest Science, 2025)

Epidemiological and clinical profiles of respiratory syncytial virus infections in hospitalized children: a retrospective cohort study utilizing targeted next-generation sequencing - Chunyun Fu; Jialing Ruan; Lishai Mo; Jiangyang Zhao; Junming Lu; Ya Huang; Xuehua Hu; Qiang Huang; Yanhua Feng; Wenting Tang; Ning Zhu; Cuihong Lu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

A facile colorimetric sensor based on Fe3O4 magnetic nanoparticles with intrinsic catalytic activity for the rapid and selective detection of ochratoxin A - Xiao Liang; Qiu-Lan Li; Ji-Tao Li; Wen-Bo Zhao; De-Zhi Yang; Ya-Ling Yang; Zi-Tao Zhong (Food Chemistry, 2025)

Three new caryophyllene-type sesquiterpenoid glycosides from Biebersteinia heterostemon maxim - Qing Li; Wen-Jian Gu; Ya-Mei Zhang; Guo-Yue Zhong; Pu-Zhao Zhang (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A novel dual-responsive NIR fluorescent probe based on isophorone: Real-time detection of Al3 + in vivo and colorimetric sensing of pH through smartphone - Ya-Tong Liu; Yue Hou; Si-Yi Yao; Ke-Yu Zhao; Han-Wen Cui; Meng-Xun Zhang; Hao Wang; Yue-Li Zou; Li-Xia Zhao (Journal of Environmental Chemical Engineering, 2025)

Effects of isoprene on the ozonolysis of Δ3-carene and β-caryophyllene: Mechanisms of secondary organic aerosol formation and cross-dimerization - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Journal of Environmental Sciences, 2025)

Unlocking the chemical basis of fermented golden pompano (Trachinotus ovatus) inoculated with indigenous Bacillus subtilis: Focus on the role of lipid oxidation on volatile flavor formation - Huifang Wang; Yanyan Wu; Shengjun Chen; Yongqiang Zhao; Chunsheng Li; Huan Xiang; Di Wang; Ya Wei; Yueqi Wang (Food Chemistry, 2025)

Engineered scallion-derived exosomes boosting small intestinal submucosa patches for gastrointestinal anastomosis and regeneration - Xudong Peng; Chaozheng Xie; Pengfei Wei; Ya Li; Anqi Cheng; Wei Jing; Yan Zhang; Bo Zhao; Yiqian Huang; Zhengqiang Wei (Chemical Engineering Journal, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Coat protein I genes are essential for the morphogenesis of the intestinal tract in Locusta migratoria - Xiaojian Liu; Mingzhu Ji; Ya Gao; Yao Li; Zhangwu Zhao; Jianzhen Zhang (Pesticide Biochemistry and Physiology, 2025)

A near-infrared multifunctional fluorescent bio-probe with large stokes shift and high quantum yield for effective determination of heavy metal lead and pesticide glyphosate in vitro and vivo - Ya-Tong Liu; Qian-Qian Zhang; Si-Yi Yao; Ke-Yu Zhao; Han-Wen Cui; Hua-Yong Zhao; Jing-Yi Li; Yue-Li Zou; Li-Xia Zhao (Journal of Hazardous Materials, 2025)

Effect of polystyrene micro/nanoplastics on PCBs removal in constructed wetlands planted with Myriophyllum aquaticum - Shuang Wang; Jun Liu; Rongjie Kang; Ya Liu; Xuan Zhao; LiTing Wang; Zhaocheng Wu; Yan Lei; Jibing Li (Environmental Research, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

Genome-wide identification and expression of Oryza sativa haloacid dehalogenase genes associated with oxadiazon metabolism - Zhao Jie Chen; Ya Nan Qu; Jun Jin Lu; Si Ying Li; Gan Ai; Xu Zhen Shi; Li Qing Zeng; Xiao Liang Liu; Dan Lu (Genetic Resources and Crop Evolution, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Membrane transport engineering for efficient yeast biomanufacturing - Xin-Yue Li; Ming-Hai Zhou; Du-Wen Zeng; Yi-Fan Zhu; Feng-Li Zhang; Sha Liao; Ya-Chao Fan; Xin-Qing Zhao; Lin Zhang; Feng-Wu Bai (Bioresource Technology, 2025)

Induction of callus and establishment of suspension culture system in Cassia mimosoides herb - Ming Zhai; Qian-qian Dai; Ying Zhao; Shengyuan Zhang; Ya-li Yang (In Vitro Cellular & Developmental Biology - Plant, 2025)

SOX21-AS1 Augmented Cervical Cancer Growth by Triggering FZD3 to Activate the Wnt/β-Catenin Signaling Pathway - Yanfang Zhi; Peipei Du; Ya Li; Hui Liu; Tao Jiang; Xin Zhao; Xiaofu Li (Biochemical Genetics, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

High glucose induces renal tubular epithelial cell senescence by inhibiting autophagic flux - Ying Zhang; Yu Zhao; Yu-Qiu Liu; Ya-Ping Fang; Li Sun; Shan-Zhai Wei; Xiao-Dong Zhu; Xiao-Liang Zhang (Human Cell, 2025)

Electrochemistry-empowered nano-labeling for versatile aptamer-based biosensing of tumor-associated proteins - Ya Cao; Xiaomeng Yu; Yue Cao; Zichen Huang; Jiancheng Xu; Jing Zhao; Genxi Li (Chemical Engineering Journal, 2025)

Time-Dependent Transcriptional Dynamics of Contextual Fear Memory Retrieval Reveals the Function of Dipeptidyl Peptidase 9 in Reconsolidation - Wen-Ting Guo; Wen-Xing Li; Yu-Chen Liu; Ya-Bo Zhao; Lin Xu; Qi-Xin Zhou (Neuroscience Bulletin, 2025)
Numerous studies on the formation and consolidation of memory have shown that memory processes are characterized by phase-dependent and dynamic regulation. Memory retrieval, as the only representation of memory content and an active form of memory processing that induces memory reconsolidation, has attracted increasing attention in recent years. Although the molecular mechanisms specific to memory retrieval-induced reconsolidation have been gradually revealed, an understanding of the time-dependent regulatory mechanisms of this process is still lacking. In this study, we applied a transcriptome analysis of memory retrieval at different time points in the recent memory stage. Differential expression analysis and Short Time-series Expression Miner (STEM) depicting temporal gene expression patterns indicated that most differential gene expression occurred at 48 h, and the STEM cluster showing the greatest transcriptional upregulation at 48 h demonstrated the most significant difference. We then screened the differentially-expressed genes associated with that met the expression patterns of those cluster-identified genes that have been reported to be involved in learning and memory processes in addition to dipeptidyl peptidase 9 (DPP9). Further quantitative polymerase chain reaction verification and pharmacological intervention suggested that DPP9 is involved in 48-h fear memory retrieval and viral vector-mediated overexpression of DPP9 countered the 48-h retrieval-induced attenuation of fear memory. Taken together, our findings suggest that temporal gene expression patterns are induced by recent memory retrieval and provide hitherto undocumented evidence of the role of DPP9 in the retrieval-induced reconsolidation of fear memory.

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Similar tolerance of urban birds towards both benign human and lethal cat predators - Hong-Yan Ye; Jing Yu; Kang Hong; Ya-Lian Li; Jin-Ming Zhao (Journal of Ornithology, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Per- and poly-fluoroalkyl substances (PFAS) accelerate biological aging mediated by increased C-reactive protein - Zongxi Zhao; Jiayan Zhou; Anye Shi; Jingyi Wang; Hongzheng Li; Xiangjun Yin; Jialiang Gao; Ying Wu; Jinlin Li; Ya Xuan Sun; Hao Yan; Yige Li; et al. (Journal of Hazardous Materials, 2024)

Nanocochleates as novel delivery vehicles for enhancement of water solubility, stability and controlled release of dihydromyricetin in gastrointestinal tract - Mohammad Molaveisi; Li Li; Jiao Yu; Ya Zhao; Qilong Shi (Food Research International, 2024)

Sericin peptides alleviate dextran sulfate-induced ulcerative colitis symptoms by modulating the Th17 cell differentiation pathway in C57BL/6 mice - Hongtao Zhu; Zhi-Jing Ni; Qian Zhong; Wei Wang; Ya-Jing An; Kiran Thakur; Jian-Guo Zhang; Zhong-Li Chen; Zhao-Jun Wei (Food Bioscience, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Retraction Note: MiR-125 family improves the radiosensitivity of head and neck squamous cell carcinoma - Qi-Wei Wang; Ya-Nan Sun; Li-Jun Tan; Jian-Nan Zhao; Xiao-Jie Zhou; Tian-Jiao Yu; Jiang-Tao Liu (Molecular Biology Reports, 2024)

Plant Functional Traits Modulate Effects of Drought on C:N:P Stoichiometry of Plant, Litter, and Soil Microbe in an Arid Grassland - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Xiangyun Li; Ya Hu; Jingjuan Qiao; Ping Yue; Min Chen; Shaokun Wang; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2024)

Optical fiber fluorescence Cu2+ sensing technology based on CdSe/ZnS quantum dots: Large detection range, low detection limit - Ya-nan Zhang; Wenchao Liang; Like Li; Hongrui Zhang; Shangwen Cao; Bo Han; Yong Zhao (Analytica Chimica Acta, 2024)

Mendelian randomization reveals predictive, preventive, and personalized insights into inflammatory bowel disease: the role of gut microbiome and circulating inflammatory proteins - Wuqing Zhao; Shixiao Li; Qianqian Li; Qiang Li; Ya Zheng; Hong Lu (EPMA Journal, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Amelioration activity of the high bioaccessible chrysanthemum (Gongju) phenolics on alcohol-induced oxidative injury in AML-12 cells - Yi-Long Ma; Zhi Li; Zheng-Fang Wu; Qian-Lan Wu; Xin Guo; Ya-Fang Shang; Kiran Thakur; Zhao-Jun Wei (Food Chemistry, 2024)

Antiallodynic and antihyperalgesic effects of decursin associated with correcting mitochondrial dysfunction and oxidative stress in type 1 diabetic mice - Li Ma; You-Ya Fan; Ben-Ling Li; Feng Xu; Xin Zhao (Chemico-Biological Interactions, 2024)

Effects of NOx and NH3 on the secondary organic aerosol formation from α-pinene photooxidation - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2024)

Understanding the mechanisms and potential pathways of soil carbon sequestration from the biogeochemistry perspective - Xiaojuan Feng; Guohua Dai; Ting Liu; Juan Jia; Erxiong Zhu; Chengzhu Liu; Yunpeng Zhao; Ya Wang; Enze Kang; Jun Xiao; Wei Li (Science China Earth Sciences, 2024)

Estimation of Regional Evapotranspiration Based on the Decouple Model and Remote Sensing Information ——a Case Study in Beijing City and Nearby Region - Su-Chuang Di; Zhao-Liang Li; Yanmin Ren; Meng Liu; Ya-Zhen Jiang; Fan-Dong Zheng; Xue-Min Li; Yan-Bing Qi; Hong-Lu Liu; Ronglin Tang (International Journal of Remote Sensing, 2024)

Nrf2 deficiency exacerbated pulmonary pyroptosis in maternal hypoxia-induced intrauterine growth restriction offspring mice - Dan Chen; Ling-yun Man; Ying-ying Wang; Wei-ying Zhu; Hui-min Zhao; Sheng-peng Li; Yan-li Zhang; Shuai-chao Li; Ya-xian Wu; Ling-Ai; Qing-feng Pang (Reproductive Toxicology, 2024)

Rapid and selective removal of bisphenol S from environmental samples by surface-imprinted polymer synthesized based on metal-organic framework MIL-101(Cr) - Kaixin Zhao; Xian Li; Guohao Cheng; Lin Liu; Runan Chen; Ya Jiao; Yongli Liu; Guifen Zhu (Journal of Environmental Chemical Engineering, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Strong electronic coupling between Ni-based MOF and Ni2P enables high-efficiency oxygen evolution reaction for various application scenarios - Yirong Wang; Xuan Yu; Zhonghong Xia; Xuanrong Li; Ya Gao; Jing Zhang; Wuliang Feng; Xingli Zou; Yufeng Zhao (Chemical Engineering Journal, 2024)

Dual-recognition “turn-off-on” fluorescent Biosensor triphenylamine-based continuous detection of copper ion and glyphosate applicated in environment and living system - Ya-Tong Liu; Qian-Qian Zhang; Si-Yi Yao; Han-Wen Cui; Yue-Li Zou; Li-Xia Zhao (Journal of Hazardous Materials, 2024)

Competition between discharge reaction and side reaction for anode's lithium during internal short circuit in lithium-ion batteries - Cong-jie Wang; Yan-li Zhu; Tao Zhang; Jun Tian; Fei Gao; Yong Zhao; Xin-ya Bu; Ting Quan (Journal of Cleaner Production, 2024)

Zirconium isotope tracing of the magmatic-hydrothermal transition - Er-Lin Zhu; Qiong-Xia Xia; Shao-Bing Zhang; James Van Orman; Ren-Xu Chen; Zhao-Ya Li; Peng Gao (Geochimica et Cosmochimica Acta, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Correlation analysis of phosphorylation of myofibrillar protein and muscle quality of tilapia during storage in ice - Ye Yu; Ya Wei; Shengjun Chen; Yueqi Wang; Hui Huang; Chunsheng Li; Di Wang; Wenzheng Shi; Jun Li; Yongqiang Zhao (Food Chemistry, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Multi-medium residues and ecological risk of herbicides in a typical agricultural watershed of the Mollisols region, Northeast China - Hanqiang Liu; Rui Li; Wenyou Hu; Le Jian; Biao Huang; Ya'nan Fan; Yongcun Zhao; Hongyan Zhang; Khalid Saifullah Khan (Science of The Total Environment, 2024)

Comprehensive analyses show the enhancement effect of exogenous melatonin on fluroxypyr-meptyl multiple phase metabolisms in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Si Ying Li; Ya Nan Qu; Gan Ai; Yan Hui Wang; Dong Jin Pan; Hao Wen Wang; Dan Lu; Xiao Liang Liu (Pesticide Biochemistry and Physiology, 2024)

Evaluating the effects of laver cultivation on tidal flat erosion: Toward sustainable environmental practices - Dezhi Chen; Gaocong Li; Jieping Tang; Lintao Zhao; Ya Ping Wang; Chao Gao (Journal of Environmental Management, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Placenta-targeted Treatment Strategies for Preeclampsia and Fetal Growth Restriction: An Opportunity and Major Challenge - Jianjian Cui; Zejun Yang; Ruilin Ma; Wencong He; Hui Tao; Ya’nan Li; Yin Zhao (Stem Cell Reviews and Reports, 2024)
The placenta plays a crucial role in maintaining normal pregnancy. The failure of spiral artery remodeling (SAR) is a key factor leading to placental ischemia and poor perfusion which is strongly associated with obstetric diseases, including preeclampsia (PE) and fetal growth restriction (FGR). Existing interventions for PE and FGR are limited and termination of pregnancy is inevitable when the maternal or fetus condition deteriorates. Considering the safety of the mother and fetus, treatments that may penetrate the placental barrier and harm the fetus are not accepted. Developing targeted treatment strategies for these conditions is urgent and necessary. With the proven efficacy of targeted therapy in treating conditions such as endometrial cancer and trophoblastic tumors, research on placental dysfunction continues to deepen. This article reviews the studies on placenta-targeted treatment and drug delivery strategies, summarizes the characteristics proposes corresponding improvement measures in targeted treatment, provides solutions for existing problems, and makes suggestions for future studies. Graphical abstract

Evolutionary and functional analysis of metabotropic glutamate receptors in lampreys - Ruyu Zhuang; Zihao Yan; Yicheng Gao; Ayqeqan Nurmamat; Shuyuan Zhang; Min Xiu; Yuesi Zhou; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Nano‑selenium alleviates cadmium-induced blood-brain barrier destruction by restoring the Wnt7A/β-catenin pathway - Chen-Xi Li; Milton Talukder; Zhao-Yi Wang; Shi-Yong Zhu; Ya-Ru Xu; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Carbonized polymer dots-based molecular imprinting: An adsorbent with enhanced selectivity for highly efficient recognition and removal of ceftiofur sodium from complex samples - Li Wang; Lin Liu; Runan Chen; Ya Jiao; Kaixin Zhao; Yongli Liu; Guifen Zhu (Journal of Hazardous Materials, 2024)

Long-term polystyrene nanoparticles exposure reduces electroretinal responses and exacerbates retinal degeneration induced by light exposure - Jincan He; Shiyi Xiong; Wenchuan Zhou; Hao Qiu; Yuqing Rao; Ya Liu; Guiyan Shen; Peiquan Zhao; Guangquan Chen; Jing Li (Journal of Hazardous Materials, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Hydroxyl-containing triazine-based conjugated microporous polymers for solid phase extraction of fluoroquinolone antibiotics in the environment and food samples - Lu-Shu Meng; Xiao-Li Wang; Xia Wang; Lei Ji; Lei-Lei Wang; Ya-Qi Cai; Ru-Song Zhao (Food Chemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Research on the screening and inhibition mechanism of angiotensin I-converting enzyme (ACE) inhibitory peptides from tuna dark muscle - Xin-Yu Zu; Ya-Nan Zhao; Yan Liang; Ying-Qiu Li; Chen-Ying Wang; Xiang-Zhong Zhao; Hua Wang (Food Bioscience, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

In-situ and label-free measurement of cytochrome C concentration with a Ti2C-MXene sensitized fiber-optic MZI sensor - Po Jin; Ya-nan Zhang; Zhong Li; Wanlu Zheng; Liangliang Cheng; Like Li; Xuegang Li; Yong Zhao (Analytica Chimica Acta, 2024)

The carbon footprint of fast fashion consumption and mitigation strategies-a case study of jeans - Zhikun Li; Ya Zhou; Minyi Zhao; Dabo Guan; Zhifeng Yang (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Esterified wheat bran: Physicochemical properties, structure and quality improvement of Chinese steamed bread during refrigerated storage - Hua Li; Qingfeng Wu; Yanyan Guo; Ya Dai; Yali Ping; Zhenzhen Chen; Beibei Zhao (Food Chemistry, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

Enhancement of adsorption performance for I2 and Cr(VI) by the metal-organic framework UiO-66-NH2 via post-synthetic modification - Ya-Yu Zhao; Zhen Xu; Xin Chen; Meng-Qiang Deng; Peng Li; Wei Gao; Ji-Yang Li; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2024)

Interfacial Si–O–Zr bonds induced well dispersed zirconia on magnetic mesoporous silicas for enhanced tetracycline removal - Li-Jia Xie; Ying Tan; Yu-Qiu Ke; Kang-Qiang Lu; Kai Yang; Dan Li; Wei-Ya Huang; Yong-Cai Zhang; Zhao-Qing Liu (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Plant functional traits mediate the response magnitude of plant-litter-soil microbial C: N: P stoichiometry to nitrogen addition in a desert steppe - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Jingjuan Qiao; Hu Ya; Xiangyun Li; Ping Yue; Min Chen; Shaokun Wang; Eduardo Medina-Roldán (Science of The Total Environment, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Insights into the differential molecular response of non-germinated and germinated spores of Ameson portunus in vitro by comparative transcriptome analysis - Zhao-Zhe Xin; Zhi-Qiang Zhu; Jiu-Yang Chen; Ya-Li Xu; Xin-Tong Zhang; Jin-Yong Zhang (Journal of Invertebrate Pathology, 2024)

Clinical and genetic architecture of a large cohort with auditory neuropathy - Hongyang Wang; Liping Guan; Xiaonan Wu; Jing Guan; Jin Li; Nan Li; Kaili Wu; Ya Gao; Dan Bing; Jianguo Zhang; Lan Lan; Tao Shi; et al. (Human Genetics, 2024)
Auditory neuropathy (AN) is a unique type of language developmental disorder, with no precise rate of genetic contribution that has been deciphered in a large cohort. In a retrospective cohort of 311 patients with AN, pathogenic and likely pathogenic variants of 23 genes were identified in 98 patients (31.5% in 311 patients), and 14 genes were mutated in two or more patients. Among subgroups of patients with AN, the prevalence of pathogenic and likely pathogenic variants was 54.4% and 56.2% in trios and families, while 22.9% in the cases with proband-only; 45.7% and 25.6% in the infant and non-infant group; and 33.7% and 0% in the bilateral and unilateral AN cases. Most of the OTOF gene (96.6%, 28/29) could only be identified in the infant group, while the AIFM1 gene could only be identified in the non-infant group; other genes such as ATP1A3 and OPA1 were identified in both infant and non-infant groups. In conclusion, genes distribution of AN, with the most common genes being OTOF and AIFM1 , is totally different from other sensorineural hearing loss. The subgroups with different onset ages showed different genetic spectrums, so did bilateral and unilateral groups and sporadic and familial or trio groups.

Cadmium promotes the binding and centrosomal translocation of CCDC85C and PLK4 via ROS-GCLM pathway to trigger centrosome amplification in colon cancer cells - Ya Wen Han; Si Xian Xu; Jun Zhang; Yuan Fei Li; Peng Xu; Shao Chin Lee; Ji Zhong Zhao (Toxicology Letters, 2024)

Road dust exposure and human corneal damage in a plateau high geological background provincial capital city: Spatial distribution, sources, bioaccessibility, and cytotoxicity of dust heavy metals - Zi-Yue Yang; Hai Liu; Jing-Ya Li; Ya-Bo Bao; Ji Yang; Li Li; Zi-Yu Zhao; Qin-Xiang Zheng; Ping Xiang (Science of The Total Environment, 2024)

Growing-season drought and nitrogen addition interactively impair grassland ecosystem stability by reducing species diversity, asynchrony, and stability - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

Evaluating the water footprint and nutritional quality of takeaway dishes for selected large cities in China - Mpiya Kapalata Frederic; Xinyu Guo; Xu Zhao; Harold Lyonel Feukam Nzudie; Martin R. Tillotson; Ya Zhou; Yiping Li (Science of The Total Environment, 2024)

Simultaneous removal of phosphate and dissolved organic matter from wastewater by MgO-doped magnetic biochar: Binary adsorption and interaction mechanism - Yue Yin; Ya-nan Luan; Yanming Xu; Zhuo Zhao; Yihua Xiao; Xianzhi Li; Changqing Liu (Journal of Water Process Engineering, 2024)

In vitro digestibility and hepato-protective potential of Lophatherum gracile Brongn. leave extract - Yi-Long Ma; Zheng-Fang Wu; Zhi Li; Yue Wang; Ya-Fang Shang; Kiran Thakur; Zhao-Jun Wei (Food Chemistry, 2024)

Novel active composite films based on carboxymethyl cellulose and sodium alginate incorporated with phycocyanin: Physico-chemical, microstructural and antioxidant properties - Hafiz Muhammad Saleem Akhtar; Ya Zhao; Li Li; Qilong Shi (Food Hydrocolloids, 2024)

Self-harm and interpersonal violence due to high temperature from the global burden of disease study 2019: A 30-year assessment - Hao Zhao; Li He; Ce Liu; Xiaobing Shan; Chunyan Gui; Ling Zhang; Yunhui Yu; Ya Xiao; Jia Xue; Kai Zhang; Bin Luo (Environmental Research, 2024)

Effects of NO and SO2 on the secondary organic aerosol formation from isoprene photooxidation - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Atmospheric Environment, 2024)

Study on the variation characteristics of ionospheric F2 layer in Qinghai-Tibet plateau and surrounding areas - Ya-Xin Liu; Hai-Sheng Zhao; Li-Xia Yang; Shu-Ji Hao; Zheng-Wen Xu (Advances in Space Research, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Plant composition change mediates climate drought, nitrogen addition, and grazing effects on soil net nitrogen mineralization in a semi-arid grassland in North China - Peng Lv; Shanshan Sun; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Ping Yue; Xiaoan Zuo (Science of The Total Environment, 2024)

The decomposition of algae has a greater impact on heavy metal transformation in freshwater lake sediments than that of macrophytes - Si-Min Xue; Shu-Qi Jiang; Rui-Ze Li; Yi-Ying Jiao; Qun Kang; Li-Ya Zhao; Zhao-hua Li; Mo Chen (Science of The Total Environment, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Exploring the mechanism of Icariin in the treatment of depression through BDNF-TrkB pathway based on network pharmacology - Xiaoke Di; Meiyu Wan; Ya-nan Bai; Fengjuan Lu; Minghui Zhao; Zhifei Zhang; Yang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Isolation and characterization of 55 SNP markers in Triplophysa (Hedinichthys) yarkandensis macroptera - Qiang Li; Yeyu Chen; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Jiansheng Lai; Xiaoyun Wu; Mingjiang Song; Feiyang Li; Ya Liu (Conservation Genetics Resources, 2023)

Uptake, translocation, accumulation, and metabolism of fluroxypyr-meptyl and oxidative stress induction in rice seedling - Zhao Jie Chen; Hao Wen Wang; Si Ying Li; Yong Heng Zhang; Ya Nan Qu; Zhi Hai He; Xue Sheng Li; Xiao Liang Liu (Environmental Science and Pollution Research, 2023)

Porosity prediction in tight sandstone reservoirs based on a one–dimensional convolutional neural network–gated recurrent unit model - Su-Zhen Shi; Gui-Fei Shi; Jin-Bo Pei; Li-Li; Kang Zhao; Ya-Zhou He (Applied Geophysics, 2023)

K252a inhibition of sperm viability for efficient crossbreeding of hermaphroditic bivalves - Tian Liu; Huilan Wei; Lijing Zhang; Liangjie Liu; Yajuan Li; Ya Shu; Yaxin Yang; Baojun Zhao; Qiang Xing; Qifan Zeng; Chunde Wang; Shi Wang; et al. (Aquaculture, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Determination of volatile compounds in different parts of grass carp using GC✕GC-MS combined with chemometrics - Guoqiang Zhao; Ya Yuan; Hong Zhou; Li Zhao; Yong Jiang (Food Bioscience, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Environmentally-friendly, sustainable ScCO2-assisted fabrication of poly (lactic acid)/ramie fiber composite foams - Jiao Li; Yingxiao Wang; Jun Lin; Ya Liu; Guilong Wang; Dong Quan; Yanjin Guan; Guoqun Zhao; Shengcheng Ji (Journal of Cleaner Production, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Melatonin attenuates cholestatic liver injury via inhibition of the inflammatory response - Ya Tan; Nan Zhao; Qiaoling Xie; Ziqian Xu; Jin Chai; Xiaoxun Zhang; Yan Li (Molecular and Cellular Biochemistry, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Leveraging opportunity of low carbon transition by super-emitter cities in China - Heran Zheng; Zengkai Zhang; Erik Dietzenbacher; Ya Zhou; Johannes Többen; Kuishuang Feng; Daniel Moran; Meng Jiang; Yuli Shan; Daoping Wang; Xiaoyu Liu; Li Li; et al. (Science Bulletin, 2023)

Sesquiterpene coumarins from Ferula sinkiangensis and their anti-pancreatic cancer effects - Jia-Lin Wang; Chun-Yan Sang; Jun Wang; Pei-Lin Li; Tian Chai; Mohammad Reza Naghavi; Ya-Min Zhao; Jun-Li Yang (Phytochemistry, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

Multi-trait functional diversity predicts ecosystem multifunctionality under nitrogen addition in a desert steppe - Ya Hu; Aixia Guo; Xiangyun Li; Ping Yue; Shenglong Zhao; Peng Lv; Xiaoan Zuo (Plant and Soil, 2023)

Conditioned medium of human menstrual blood-derived endometrial stem cells protects against cell inflammation and apoptosis of Npc1KO N2a cells - Minlin Yang; Yanchun Zhao; Xiaoying Li; Han Li; Fangfang Cheng; Yanli Liu; Zisen Jia; Ya’nan He; Juntang Lin; Lihong Guan (Metabolic Brain Disease, 2023)

Megastigmane sesquiterpenoids from Saussurea medusa and their anti-inflammatory activities - Jing-Ya Cao; Qi Dong; Zhi-Yao Wang; Ye Zhao; Yu Ren; Li-Juan Mei; Yan-duo Tao; Rui-Tao Yu (Natural Product Research, 2023)

Isolation and identification of Eurasian avian-like H1N1 swine influenza virus and evaluation of their pathogenicity and immune protective effects in pigs - Ying Yang; Yunfu Huang; Kun Huang; Yufei Zhang; Xiaotong Hu; Weihua Zou; Chao Wu; Xianfeng Hui; Chengfei Li; Ya Zhao; Xiaomei Sun; Zhong Zou; et al. (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Corrigendum to “Rno_circRNA_006061 participates in apoptosis induced by formaldehyde via activating p38/ATF3 pathway” [Chem. Biol. Interact. 381 (2023) 110584] - Pan Ge; Xue-wei Yuan; Xiang Zhang; Zhi-hao Liu; Si-yu Wang; Yan-qi Yang; Qian-nan Wang; Li-jian Qian; Ya-zhao Li; Dang-xia Zhou (Chemico-Biological Interactions, 2023)

Study of polycyclic aromatic hydrocarbons accumulation in bioretention facilities and its influence on microbial community structure - Ya-jiao Li; Yan-ting Shi; Ling-zhi Zhao; Ya-fang Li; Jia-ping Wang; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Corrigendum to “Semaphorin3A regulates mitochondrial apoptosis in RAW264.7 cells in vitro” [Tissue Cell 75 (2022) 101711] - Zhongkui Guo; Yi Li; Ming Chen; Ya Gu; Yang Chen; Yanpeng Zhao; Peifu Tang (Tissue and Cell, 2023)

Rno_circRNA_006061 participates in apoptosis induced by formaldehyde via activating p38/ATF3 pathway - Pan Ge; Xue-wei Yuan; Xiang Zhang; Zhi-hao Liu; Si-yu Wang; Yan-qi Yang; Qian-nan Wang; Li-jian Qian; Ya-zhao Li; Dang-xia Zhou (Chemico-Biological Interactions, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

Hexavalent chromate bioreduction by a magnetotactic bacterium Magnetospirillum gryphiswaldense MSR-1 and the effect of magnetosome synthesis. - Siang Chen Wu; Wei-Che Hsiao; Ya-Chun Zhao; Li-Fen Wu (Chemosphere, 2023)

New insights into the phylogeny and evolution of Chinese Ovophis (Serpentes, Viperidae): Inferred from multilocus data - Yang‐Mei Zeng; Ke Li; Qin Liu; Ya‐Yong Wu; Shao‐Bing Hou; Gui‐Gang Zhao; Sang Ngoc Nguyen; Peng Guo; Lei Shi (Zoologica Scripta, 2023)
The Asian pitviper genus Ovophis is a group of venomous snakes widely distributed in mid to high elevation mountains in Asia, and presently five species are recognised. However, its systematics, species diversity and species distribution boundaries remain poorly understood. We reconstructed the phylogenetic relationships and explored species diversity of Chinese Ovophis based on two mitochondrial fragments (Cyt b and ND4) and four nuclear genes ( BACH1 , c‐mos , Rag1 , NT3 ) and also conducted a morphological comparison between focal species. Our results indicated that the species diversity had been underestimated within Ovophis and we described a population from southern Yunnan, China, as a new taxon, naming it as Ovophis malhotrae sp . nov . Based on more extensive sampling, we redefined the distribution of O. monticola and O. makazayazaya in China. Divergence date estimation suggested that Ovophis originated at about 16.79 Ma in the middle Miocene.

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Pathway, flux and accumulation of pollutant emission from landfill receiving As- and Hg-containing hazardous waste - Shu Li; Manying Zhao; Ya Xu; Qifei Huang; Guangyuan Yao; Yuqiang Liu; Yuxin Zhao (Journal of Cleaner Production, 2023)

Rapid identification of high and low cadmium (Cd) accumulating rice cultivars using machine learning models with molecular markers and soil Cd levels as input data - Zhong Tang; Ting-Ting You; Ya-Fang Li; Zhi-Xian Tang; Miao-Qing Bao; Ge Dong; Zhong-Rui Xu; Peng Wang; Fang-Jie Zhao (Environmental Pollution, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

RETRACTED ARTICLE: MiR-125 family improves the radiosensitivity of head and neck squamous cell carcinoma - Qi-Wei Wang; Ya-Nan Sun; Li-Jun Tan; Jian-Nan Zhao; Xiao-Jie Zhou; Tian-Jiao Yu; Jiang-Tao Liu (Molecular Biology Reports, 2023)
Background MiRNAs can affect the radiosensitization of head and neck squamous cell carcinoma (HNSCC). We aimed to analyze the function of miR-125 family members in HNSCC using The Cancer Genome Atlas (TCGA) and determine their effect on radiation in laryngeal squamous cell cancer (LSCC). Methods First, we systematically analyzed the role of the miR-125 family in HNSCC using the TCGA database and found that miR-125a-5p is associated with radiotherapy. We then performed comprehensive enrichment analysis of miR-125a-5p and predicted target genes. Then, we performed transfection, cell proliferation assays, reverse transcription polymerase chain reaction, apoptosis assays, micronucleus tests, and western blotting on hep-2 cells selected with puromycin. Results MiR-125 family members exhibited significantly different expression in HNSCC. They were significantly associated with tumor–node–metastasis staging, clinical stages, and histological grades. Radiation therapy had a statistically effect on miR-125 family members, except miR-125a-3p. Moreover, miR-125a-5p was related to overall survival in LSCC. Thus, we predicted 110 target genes and seven hub genes of miR-125a-5p. The proliferation rate of cells transfected with lentivirus vector expressing miR-125a-5p was significantly reduced compared to the other groups. The radiation effect was enhanced in cells transfected with miR-125a-5p. The ratio of apoptotic cells transfected and exposed to X-rays (10 Gy) was distinctly higher than that of the Ad-control group. Western blotting analysis revealed that miR-125a-5p upregulated the apoptotic regulators P53 and rH2AX. Thus, miR-125a-5p may increase radiosensitivity in LSCC via upregulation of pro-apoptotic genes. Conclusions MiR-125 family members could be prognostic biomarkers of HNSCC and improve HNSCC sensitivity to radiotherapy by activating P53. Upregulating miR-125a-5p via lentivirus vectors may be a novel strategy to strengthen the effect of radiotherapy on LSCC.

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Ying-Xin Zhao; Jin-Long Li (Environmental Pollution, 2023)

Efficient removal of Hg0 in flue gas using a novel Sn-based porphyrin polymer - Zhen Li; Ya Cai; Daorong Sun; Zhaolian Ye; Songjian Zhao (Science of The Total Environment, 2023)

Periploca sepium leaf dry weight, area, and thickness scale differently under different light environments in Taohe riparian forests - Min Ma; Cheng-Zhang Zhao; Man-Ping Kang; Xiao-Ya Li; Zhi-Wei Zhang; Xu-Qian Bai (Flora, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Grazing impairs ecosystem stability through changes in species asynchrony and stability rather than diversity across spatial scales in desert steppe, Northern China - Shanshan Sun; Shenglong Zhao; Xinping Liu; Peng Lv; Maowei Liang; Yulin Li; Ya Hu; Xiaoan Zuo (Agriculture, Ecosystems & Environment, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR - Jin J. Li; Ya X. Yue; Jie F. Jiang; Sheng J. Shi; Hui X. Wu; Yuan H. Zhao; Fei F. Che (Chemosphere, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

Multiple generations of garnet, zircon and titanite: Temporal constraints on Fe skarn mineralization in the Middle-Lower Yangtze River Valley Metallogenic Belt, eastern China - Zhao-Ya Li; Qiong-Xia Xia; Yi-Xin Liu (Lithos, 2023)

Compositional changes of CH, O, and N moieties in petroleum ether-extractable portions from the three-step mild degradation of Dongming lignite - Yan-Jun Li; Wei Zhao; Guang-Hui Liu; Hao-Dong An; Ya-Jun Ma; Yu-Hong Kang; Yong Gao; Ni Bai; Ding-Kai Wang; Xian-Yong Wei; Hong-Cun Bai (Fuel, 2023)

Morphology evolution regulation of dual-doped S, Fe-NiMoO4 microrods based on precipitation-dissolution equilibrium for oxygen evolution - Meng-Xuan Li; Bo Xiao; Zi-Yi Zhao; Yu Ma; Ya-Nan Zhou; Xin-Yu Zhang; Feng-Ge Wang; Yong-Ming Chai; Bin Dong (Fuel, 2023)

Unraveling the antibacterial mechanism of Lactiplantibacillus plantarum MY2 cell-free supernatants against Aeromonas hydrophila ST3 and potential application in raw tuna - Di Wang; Yangfan Liu; Xupeng Li; Shengjun Chen; Jianchao Deng; Chunsheng Li; Chuang Pan; Yueqi Wang; Huan Xiang; Yang Feng; Xianqing Yang; Laihao Li; et al. (Food Control, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

Effects of altered precipitation patterns on soil nitrogen transformation in different landscape types during the growing season in northern China - Peng Lv; Shanshan Sun; Xueyong Zhao; Yuqiang Li; Shenglong Zhao; Jing Zhang; Ya Hu; Aixia Guo; Ping Yue; Xiaoan Zuo (CATENA, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Effect of molding on the structure and properties of poly(butylene adipate-co-terephthalate)/poly(propylene carbonate)/organically modified montmorillonite nanocomposites - Yang Zhao; Jinqing Lai; Ya Huang; Hong Jiang; Yongrong Sun; Yuyin Li; Yuan Li; Fayong Li; Zhengtang Luo; Dong Xie (Applied Clay Science, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Establishment of an efficient method for kiwifruit in vitro micrografting - Wantian Yao; Lingling Kong; Diya Lei; Bing Zhao; Honglan Tang; Xuan Zhou; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Oral administration of Bacillus cereus GW-01 alleviates the accumulation and detrimental effects of β-cypermethrin in mice - Yangdan Jiang; Ying Liao; Chaojin Si; Juan Du; Chen Xia; Ya-nan Wang; Gang Liu; Qi Li; Jiayuan Zhao (Chemosphere, 2023)

H3K4me3 as a target of di(2-ethylhexyl) phthalate (DEHP) impairing primordial follicle assembly - Ming-Hao Li; Jun-Jie Wang; Yan-Qin Feng; Xuan Liu; Zi-Hui Yan; Xiao-Jun Zhang; Ya-Xin Wen; Hao-Wei Luo; Lan Li; Massimo De Felici; Ai-Hong Zhao; Wei Shen (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution - Yue-Jun Li; Yong-Jin Gao; Hui Zhou; Guang-Ya Zhang; Lei Wen; Yan Zhao; Cheng Li; Duo-Ming Zheng; Ya-Lei Liu; Hong-Hui Li; Cai-Ming Luo; Tong-Fei Huang; et al. (Journal of Asian Earth Sciences, 2023)

Synergistic effect of ferrous ion-activated hydrogen peroxide and persulfate on the degradation of phthalates in aquatic environments by non-target analysis - Ya Wu; Rongmiao Fang; Hao Li; Jingyao Li; Dan Zhao; NaNa Chang; Huaming Sun; Jun Shi (Chemical Engineering Journal, 2023)

Transforming growth factor-β signaling: From tissue fibrosis to therapeutic opportunities - Li-Li Ren; Xiao-Jun Li; Ting-Ting Duan; Zheng-Hai Li; Jun-Zheng Yang; Ya-Mei Zhang; Liang Zou; Hua Miao; Ying-Yong Zhao (Chemico-Biological Interactions, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Cattle Encephalon Glycoside and Ignotin Attenuates Aβ1-42-Mediated Neurotoxicity by Preventing NLRP3 Inflammasome Activation and Modulating Microglial Polarization via TLR4/NF-κB Signaling Pathway - Ya Gao; Shuyue Li; Yidan Zhang; Jian Zhang; Yuan Zhao; Cui Chang; Xuan Gao; Guofeng Yang (Neurotoxicity Research, 2022)

Phytoplankton biomass variation after cage aquaculture removal from the Daheiting Reservoir, China: observations from satellite data - Ya Xie; Hongli Zhao; Junsheng Li; Fangfang Zhang; Shenglei Wang; Ziyao Yin; Wei Shen (Hydrobiologia, 2022)

Genome-Wide Identification, Expression, and Interaction Analysis of BEL-Like Homeodomain Gene Family in Peach - Hui-feng Li; Ya-ting Wu; Qiang Zhao; Qing-long Dong (Biochemical Genetics, 2022)

The cAMP‐PKA signalling pathway regulates hyphal growth, conidiation, trap morphogenesis, stress tolerance, and autophagy in Arthrobotrys oligospora - Mei‐Chen Zhu; Na Zhao; Yan‐Kun Liu; Xue‐Mei Li; Zheng‐Yi Zhen; Ya‐Qing Zheng; Ke‐Qin Zhang; Jin‐Kui Yang (Environmental Microbiology, 2022)
The cyclic adenosine monophosphate‐protein kinase A (cAMP‐PKA) signalling pathway is evolutionarily conserved in eukaryotes and plays a crucial role in defending against external environmental challenges, which can modulate the cellular response to external stimuli. Arthrobotrys oligospora is a typical nematode‐trapping fungus that specializes in adhesive networks to kill nematodes. To elucidate the biological roles of the cAMP‐PKA signalling pathway, we characterized the orthologous adenylate cyclase AoAcy, a regulatory subunit (AoPkaR), and two catalytic subunits (AoPkaC1 and AoPkaC2) of PKA in A. oligospora by gene disruption, transcriptome, and metabolome analyses. Deletion of Aoacy significantly reduced the levels of cAMP and arthrobotrisins. Results revealed that Aoacy , AopkaR , and AopkaC1 were involved in hyphal growth, trap morphogenesis, sporulation, stress resistance, and autophagy. In addition, Aoacy and AopkaC1 were involved in the regulation of mitochondrial morphology, thereby affecting energy metabolism, whereas AopkaC2 affected sporulation, nuclei, and autophagy. Multi‐omics results showed that the cAMP‐PKA signalling pathway regulated multiple metabolic and cellular processes. Collectively, these data highlight the indispensable role of cAMP‐PKA signalling pathway in the growth, development, and pathogenicity of A. oligospora, and provide insights into the regulatory mechanisms of signalling pathways in sporulation, trap formation, and lifestyle transition.

Development of 45 SNP markers in Triplophysa hsutschouensis based on RAD sequencing - Ya Liu; Jiansheng Lai; Zhongmeng Zhao; Hongyu Ke; Han Zhao; Yeyu Chen; Xiaoyun Wu; Qiang Li (Conservation Genetics Resources, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Historical biogeography of the gingers and its implications for shifts in tropical rain forest habitats - Jian‐Li Zhao; Xiang‐Qin Yu; W. John Kress; Ya‐Li Wang; Yong‐Mei Xia; Qing‐Jun Li (Journal of Biogeography, 2022)
Aim The relationships between biome shifts and global environmental changes in temperate zone habitats have been extensively explored; yet, the historical dynamics of taxa found in the tropical rain forest (TRF) remain poorly known. This study aims to reconstruct the relationships between tropical rain forest shifts and global environmental changes through the patterns of historical biogeography of a pantropical family of monocots, the Zingiberaceae. Location Global. Taxon Zingiberaceae. Methods We sampled DNA sequences (nrITS, trn K, trn L‐ trn F and psb A‐ trn H) from GenBank for 77% of the genera, including 30% of species, in the Zingiberaceae. Global fossil records of the Zingiberaceae were collected from literatures. Rates of speciation, extinction and diversification were estimated based on phylogenetic data and fossil records through methods implemented in BAMM. Ancestral ranges were estimated using single‐tree BioGeoBEARS and multiple‐trees BioGeoBEARS in RASP. Dispersal rate through time and dispersal rate among regions were calculated in R based on the result of ancestral estimation. Results The common ancestor of the Zingiberaceae likely originated in northern Africa during the mid‐Cretaceous, with later dispersal to the Asian tropics. Indo‐Burma, rather than Malesia, was likely a provenance of the common ancestor of Alpinioideae–Zingiberoideae. Several abrupt shifts of evolutionary rates from the Palaeocene were synchronized with sudden global environmental changes. Main conclusions Integrating phylogenetic patterns with fossil records suggests that the Zingiberaceae dispersed to Asia through drift of the Indian Plate from Africa in the late Palaeocene. Formation of island chains, land corridors and warming temperatures facilitated the emigration of the Zingiberaceae to a broad distribution across the tropics. Moreover, dramatic fluctuations of the speciation rate of Zingiberoideae appear to have been synchronized with global climate fluctuations. In general, the evolutionary history of the Zingiberaceae broadens our understanding of the association between TRF shifts in distribution and past global environmental changes, especially the origin of TRF in Southeast Asia.

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Isolation and characterization of 45 SNP markers in Triplophysa tenuis - Ya Liu; Yeyu Chen; Jiansheng Lai; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Xiaoyun Wu; Jian Zhou; Qiang Li (Conservation Genetics Resources, 2022)

First report of chilli veinal mottle virus infecting tobacco in Guizhou, China - Yue Chen; Ting Ting Li; Jing Zhong; Li Ling Zhao; Ya Li Guo; Ye Chun Lin; Gui Gao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Alpha-Lipoic Acid Attenuates MPTP/MPP+-Induced Neurotoxicity: Roles of SIRT1-Dependent PGC-1α Signaling Pathways - Jian Zhang; Ya Gao; Lan Zhang; Cong Zhang; Yuan Zhao; Yidan Zhang; Shuyue Li; Cui Chang; Xiangjian Zhang; Guofeng Yang (Neurotoxicity Research, 2022)

Overexpression of Cpg15 Alleviates the Oxidative Stress in Neuronal Cells Via Regulating Redox Enzymes and Nrf2 Antioxidative Pathway - Yi Jiang; Jun-Jie Li; Ya-Wei Mu; Han-Yang Jiang; Zi-Xuan Wei; Zi-Yao Xiao; Jing-Jing Zhao; Xian-Hua Chen (Neurotoxicity Research, 2022)

Triterpenoids and lignans from Schisandra chinensis and their inhibition activities of Cdc25A/B phosphatases - Qian-Qian Zhao; Wen-Jun Wei; Ya Li; Kun Gao (Natural Product Research, 2022)

Single-cell RNA sequencing reveals Nestin+ active neural stem cells outside the central canal after spinal cord injury - Muya Shu; Xiaoyu Xue; Hu Nie; Xianming Wu; Minghan Sun; Lianyong Qiao; Xing Li; Bai Xu; Zhifeng Xiao; Yannan Zhao; Yongheng Fan; Bing Chen; et al. (Science China Life Sciences, 2022)

Antimicrobial Natural Products Produced by Soil-Derived Fungus Penicillium cremeogriseum W1-1 - Xu-Yan Sang; Zhao-Jie Wang; Ya-Bin Yang; Yong-Liang Wang; Mei-Ling Xiang; Dou-Ying Zhu; Ying Zhou; Xiao-Dong Luo; Li-Xing Zhao (Indian Journal of Microbiology, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Dynamic characteristics and drivers of the regional household energy-carbon-water nexus in China - Hao Li; Yuhuan Zhao; Lu Zheng; Song Wang; Jianing Kang; Ya Liu; Hongxian Li; Long Shi; Yuli Shan (Environmental Science and Pollution Research, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Study of pollutant accumulation characteristics and microbial community impact at three bioretention facilities - Ya-jiao Li; Heng Fu; Jing-yu Zhang; Zhao-xin Zhang; Jia-ke Li (Environmental Science and Pollution Research, 2021)

Preferential capture of phosphate by an Enteromorpha prolifera–based biopolymer encapsulating hydrous zirconium oxide nanoparticles - Qian-Qian Zhong; Li Shen; Ya-Qin Zhao; Yu-Cui Hao; Li-Cong Meng; Yan-Juan Liu; Xing Xu; Ya-Nan Shang; Bao-Yu Gao; Qin-Yan Yue (Environmental Science and Pollution Research, 2021)

Estimation of mountain block recharge on the northern Tianshan Mountains using numerical modeling - Jian-hua Ping; Ya-qiang Zhu; Xue-mei Mei; Wei Leng; Sheng Li; Ji-chang Zhao (Journal of Mountain Science, 2021)

Roles of bulk and rhizosphere denitrifying bacteria in denitrification from paddy soils under straw return condition - Ning Wang; Ya-Hui Zhao; Jian-Guang Yu; Li-Hong Xue; Hong-Bo Li; Lin-Zhang Yang (Journal of Soils and Sediments, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Retraction Note to: NPC-16, a novel naphthalimide–polyamine conjugate, induced apoptosis and autophagy in human hepatoma HepG2 cells and Bel-7402 cells - Song-qiang Xie; Qian Li; Ya-hong Zhang; Jian-hong Wang; Zi-hou Mei; Jin Zhao; Chao-jie Wang (Apoptosis, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Toxicity Changes of Heavily Polluted River Sediments on Daphnia magna Before and After Dredging - Li-Ling Zhang; Zhou-Tao Pei; Ya-Ni Zhao; Jing Zhang; Rou-Rou Xu; Meng Zhang; Wen-Qiang Wang; Li-Wei Sun; Guang-Can Zhu (Bulletin of Environmental Contamination and Toxicology, 2020)

Population pharmacokinetics and dose optimization of ceftriaxone for children with community-acquired pneumonia - Muhammad Wasim Khan; Ya-Kun Wang; Yue-E Wu; Bo-Hao Tang; Min Kan; Hai-Yan Shi; Yi Zheng; Bao-Ping Xu; A-Dong Shen; Evelyne Jacqz-Aigrain; Li-Yuan Tian; Wei Zhao (European Journal of Clinical Pharmacology, 2020)

Antagonistic effects of nano-selenium on broilers hepatic injury induced by Cr(VI) poisoning in AMPK pathway - Tian-guang Zhang; Ya-li Zhao; Lei Li; Dong-hai Zhou (Environmental Science and Pollution Research, 2020)

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice - Xiang Feng; Hui-Ying Zhao; Yu-Jin Shao; Hui-Fang Lou; Li-Ya Zhu; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2020)
Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake states in the active period in mice. Our results showed that total sleep time (time in rapid eye-movement [REM] and non-REM [NREM] sleep) increased in the active period after acute SDS. NREM sleep increased mainly during the first 3 h after SDS, while REM sleep increased at a later time. Then, we demonstrated that the increased NREM sleep had an anxiolytic benefit in acute SDS. Mice deprived of sleep for 1 h or 3 h after acute SDS remained in a highly anxious state, while in mice with ad libitum sleep the anxiety rapidly faded away. Altogether, our findings suggest an anxiolytic effect of NREM sleep, and indicate a potential therapeutic strategy for anxiety.

The effect of salt on the evolution of a subsalt sandstone reservoir in the Kuqa foreland basin, western China - Hai Wu; Mengjun Zhao; Qingong Zhuo; Xuesong Lu; Long Wang; Weiqiang Li; Ya Deng (Carbonates and Evaporites, 2020)

Characterization, tissue distribution of resistin gene and the effect of fasting and refeeding on resistin mRNA expression in Siberian sturgeon ( Acipenser baerii ) - Ni Tang; Yanlin Liu; Zhengzhi Tian; Shaoqi Xu; Mei Wang; Hu Chen; Bin Wang; Ya Li; Yan Wang; Song Yang; Liulan Zhao; Defang Chen; et al. (Journal of Fish Biology, 2020)
Resistin as an adipokine identified from rodents in 2001 is involved in many biological processes. However, little is known about this gene in fish. We cloned Siberian sturgeon ( Acipenser baerii ) resistin cDNA of 795 base pairs, encoding 107 amino acids, which showed 38–40% identity to human and rodents. Real‐time quantitative PCR showed that the resistin gene was widely distributed in tissues of Siberian sturgeon, with the highest expression in liver. After fasting for 1, 3, 6 and 10 days, the expression of the resistin gene in the liver of Siberian sturgeon decreased significantly, and after refeeding on the 10 days of fasting the resistin mRNA expression increased rapidly, suggesting that resistin may play an important role in liver in response to starvation. Taken together, these results suggest that resistin may be involved in the regulation of energy homeostasis in liver.

Arsenic, lead, and cadmium bioaccessibility in contaminated soils: Measurements and validations - Hong-Bo Li; Meng-Ya Li; Di Zhao; Jie Li; Shi-Wei Li; Ping Xiang; Albert L. Juhasz; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

An Injectable Nanocomposite Hydrogel for Potential Application of Vascularization and Tissue Repair - Yilei Ding; An-sha Zhao; Tianmei Liu; Ya-nan Wang; Yuan Gao; Jing-an Li; Ping Yang (Annals of Biomedical Engineering, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

The Arabidopsis kinase-associated protein phosphatase KAPP, interacting with protein kinases SnRK2.2/2.3/2.6, negatively regulates abscisic acid signaling - Kai Lu; Ya-Dong Zhang; Chun-Fang Zhao; Li-Hui Zhou; Qing-Yong Zhao; Tao Chen; Cai-Lin Wang (Plant Molecular Biology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

The efflux pump inhibitor tetrandrine exhibits synergism with fluconazole or voriconazole against Candida parapsilosis - Ya-Jing Zhao; Wei-Da Liu; Yong-Nian Shen; Dong-Mei Li; Kun-Ju Zhu; Hong Zhang (Molecular Biology Reports, 2019)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

Scenario analysis of ETS revenue allocation mechanism of China: based on a dynamic CGE model - Hao Li; Yuhuan Zhao; Song Wang; Jiang Lin; Ye Cao; Qiaoling Shi; Ya Liu; Yanli Xiao; Junjie Li (Environmental Science and Pollution Research, 2019)

Detection and characterization of a novel hepacivirus in long-tailed ground squirrels (Spermophilus undulatus) in China - Li-li Li; Meng-meng Liu; Shu Shen; Yu-jiang Zhang; Ya-long Xu; Hong-yan Deng; Fei Deng; Zhao-jun Duan (Archives of Virology, 2019)

Potential hypoglycemic effect of acetophenones from the root bark of Cynanchum wilfordii - Hao-Wen Jiang; Shan-Shan Gu; Lei Cao; Sheng-Shi Jiang; Jing Lin; Yan Chen; Ling Wang; He Jiao; Jing-Ya Li; Wei-Min Zhao; Jin-Long Li (Natural Product Research, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

Associations between the red blood cell distribution width and primary angle-closure glaucoma: a potential for disease prediction - Qiang Chen; Bin Zhao; Meng-ya Wang; Xue-yu Chen; Dong Li; Xin-quan Jiang; Jing-hui Tian; Yong-jun Liu (EPMA Journal, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Tolerance of two apple rootstocks to short-term salt stress: focus on chlorophyll degradation, photosynthesis, hormone and leaf ultrastructures - Yan-fang Zhu; Yu-xia Wu; Ya Hu; Xu-mei Jia; Tong Zhao; Li Cheng; Yan-xiu Wang (Acta Physiologiae Plantarum, 2019)

The Construction of Full-Length cDNA Library for Otodectes cynotis - Li Hu; Ya-e Zhao; Dong-ling Niu; Rui Yang; Ji-hui Zeng (Acta Parasitologica, 2019)

Transport Dynamics of Mercury in Rainfall-runoff After Summer Drought in a Small Agricultural Watershed in the Three Gorges Reservoir Region - Qinqin Xu; Cheng Zhang; Li Liang; Dingyong Wang; Zheng Zhao; Ya Wang; Yongmin Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Influence of shrub roots on soil macropores using X-ray computed tomography in a shrub-encroached grassland in Northern China - Xia Hu; Xiao-Yan Li; Lan-Lan Guo; Yong Liu; Pei Wang; Yun-Duo Zhao; Ya-Qian Cheng; Yan-Li Lyu; Lian-You Liu (Journal of Soils and Sediments, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Drought loss assessment combining remote sensing and a crop growth model for maize in Yunnan Province, China - Maofang Gao; Zhao-Liang Li; Sanchao Liu; Ya Gao; Pei Leng; Sibo Duan (International Journal of Remote Sensing, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Anti-Hypertensive Action of Fenofibrate via UCP2 Upregulation Mediated by PPAR Activation in Baroreflex Afferent Pathway - Jian Guan; Miao Zhao; Chao He; Xue Li; Ying Li; Jie Sun; Wei Wang; Ya-Li Cui; Qing Zhang; Bai-Yan Li; Guo-Fen Qiao (Neuroscience Bulletin, 2019)

Non-invasive Vagus Nerve Stimulation Protects Against Cerebral Ischemia/Reperfusion Injury and Promotes Microglial M2 Polarization Via Interleukin-17A Inhibition - Xiao-Ping Zhao; Yuan Zhao; Xiao-Ya Qin; Li-Yuan Wan; Xiao-Xuan Fan (Journal of Molecular Neuroscience, 2019)

Transcriptome analysis in Malus halliana roots in response to iron deficiency reveals insight into sugar regulation - Ya Hu; Yan-fang Zhu; Ai-xia Guo; Xu-mei Jia; Li Cheng; Tong Zhao; Yan-xiu Wang (Molecular Genetics and Genomics, 2018)

Development and characterization of 27 SNP markers in the Mauremys mutica transcriptome - Zhang Xin-Cheng; Zhao Jian; Li Wei; Liu Yi-Hui; Wei Cheng-Qing; Wang Ya-Kun; Ye Zhao-Yang; Zhu Xin-Ping (Conservation Genetics Resources, 2018)

Physiological and anatomical response of foliar silicon application to Dendrocalamus brandisii plantlet leaves under chilling - Hui Zhan; Li-ya Zhang; Lin Deng; Zhao-hui Niu; Mao-biao Li; Chang-ming Wang; Shuguang Wang (Acta Physiologiae Plantarum, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Gentiopicroside abrogates lipopolysaccharide-induced depressive-like behavior in mice through tryptophan-degrading pathway - Ya-ting Deng; Ming-gao Zhao; Tian-jiao Xu; Jin-Hou; Xin-hua Li (Metabolic Brain Disease, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

Effect of Bacterial Community and Free Amino Acids on the Content of Biogenic Amines During Fermentation of Yu-lu, a Chinese Fermented Fish Sauce - Yueqi Wang; Chunsheng Li; Laihao Li; Xianqing Yang; Yanyan Wu; Yongqiang Zhao; Ya Wei (Journal of Aquatic Food Product Technology, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. - Ju-cheng Zhang; Guang-Yi Chen; Xiao-Zhan Li; Ming Hu; Bang-Yan Wang; Bao-Hui Ruan; Hao Zhou; Li-Xing Zhao; Jun Zhou; Zhong-Tao Ding; Ya-Bin Yang (Natural Product Research, 2017)

Trace Element Levels in Scalp Hair of School Children in Shigatse, Tibet, an Endemic Area for Kaschin-Beck Disease (KBD) - Ya’nan Guo; Hairong Li; Linsheng Yang; Yonghua Li; Binggan Wei; Wuyi Wang; Hongqiang Gong; Min Guo; Cangjue Nima; Shengcheng Zhao; Jing Wang (Biological Trace Element Research, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

Assessment of arsenic trioxide toxicity on cock muscular tissue: alterations of oxidative damage parameters, inflammatory cytokines and heat shock proteins - Si-wen Li; Ying Guo; Ying He; Xiao Sun; Hong-jing Zhao; Yu Wang; Ya-jun Wang; Ming-wei Xing (Ecotoxicology, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Establishment of a markerless gene deletion system in Chromohalobacter salexigens DSM 3043 - Ya-Hui Shao; Li-Zhong Guo; Hao Yu; Bai-Suo Zhao; Wei-Dong Lu (Extremophiles, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

Downregulation of miR-221-3p contributes to IL-1β-induced cartilage degradation by directly targeting the SDF1/CXCR4 signaling pathway - Xin Zheng; Feng-chao Zhao; Yong Pang; Dong-ya Li; Sheng-cheng Yao; Shao-song Sun; Kai-jin Guo (Journal of Molecular Medicine, 2017)

The complete mitochondrial genome of the monophagous moth Protegira songi (Lepidoptera: Noctuidae) - Guo Xiao-Hui; Cheng Ming-Yang; Hou Ya-Feng; Deng Tuan-Tuan; Zhao Sha; Yu Hai-Li; Xing Lian-Xi (Conservation Genetics Resources, 2017)

Koninginins R-S from the endophytic fungus Trichoderma koningiopsis - Ming Hu; Qi-Ling Li; Ya-Bin Yang; Kai Liu; Cui-Ping Miao; Li-Xing Zhao; Zhong-Tao Ding (Natural Product Research, 2017)

Decomposition and scenario analysis of CO2 emissions in China’s power industry: based on LMDI method - Yuhuan Zhao; Hao Li; Zhonghua Zhang; Yongfeng Zhang; Song Wang; Ya Liu (Natural Hazards, 2017)

Effects of saline water irrigation and fertilization regimes on soil microbial metabolic activity - Li -Juan Chen; Qi Feng; Yong-Ping Wei; Chang-Sheng Li; Yan Zhao; Hui-Ya Li; Bao-Gui Zhang (Journal of Soils and Sediments, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

A new phenolic derivative with soluble epoxide hydrolase and nuclear factor-kappaB inhibitory activity from the aqueous extract of Acacia catechu - Ya Nan Sun; Wei Li; Seok Bean Song; Xi Tao Yan; Yan Zhao; A. Reum Jo; Jong Seong Kang; Kim Young Ho (Natural Product Research, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

A new coumarin isolated from Sarcandra glabra as potential anti-inflammatory agent - Maojie Wang; Jin Zhao; Ya Zhao; Run-Yue Huang; Geng Li; Xing Zeng; Xiong Li (Natural Product Research, 2016)

Research on the surface movement rules and prediction method of underground coal gasification - Huai-zhan Li; Guang-li Guo; Jian-feng Zha; Ya-fei Yuan; Bin-chen Zhao (Bulletin of Engineering Geology and the Environment, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Effect of fish oil supplement in maintenance hemodialysis patients: a systematic review and meta-analysis of published randomized controlled trials - Lei He; Meng-si Li; Mei Lin; Tian-ya Zhao; Ping Gao (European Journal of Clinical Pharmacology, 2016)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Subcellular distribution and chemical forms of cadmium in a dark septate endophyte (DSE), Exophiala pisciphila - Fangdong Zhan; Yongmei He; Yuan Li; Tao Li; Yun-Ya Yang; Gurpal S. Toor; Zhiwei Zhao (Environmental Science and Pollution Research, 2015)

Retraction Note to: Genetic polymorphisms in the CYP1A1 and CYP1B1 genes and susceptibility to bladder cancer: a meta-analysis - Yan-Zhi Chen; Jing Li; Yu-Xia Zhao; Dan Liu; He-Tong Wang; Ya Gao; Ying Chen (Molecular Biology Reports, 2015)

Promoter analysis and RNA interference of CYP6ab4 in the silkworm Bombyx mori - Guo-Dong Zhao; Yi-Ling Zhang; Yun-Lei Liu; Bing Li; Yu-Hua Chen; Ya-Xiang Xu; Qing-You Xia; Wei-De Shen; Zheng-Guo Wei (Molecular Genetics and Genomics, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

Quantitative analysis of cellular proteome alterations of Pseudomonas putida to naphthalene-induced stress - Shan-Shan Li; Xiao Hu; Hong Zhao; Ya-Xiao Li; Li Zhang; Li-Jun Gong; Jin Guo; Hua-Bing Zhao (Biotechnology Letters, 2015)

Potential dental pulp revascularization and odonto-/osteogenic capacity of a novel transplant combined with dental pulp stem cells and platelet-rich fibrin - Yong-Jin Chen; Yin-Hua Zhao; Ya-Juan Zhao; Nan-Xia Liu; Xin Lv; Qiang Li; Fa-Ming Chen; Min Zhang (Cell and Tissue Research, 2015)

Effect of dietary supplementation of Bacillus subtilis B10 on biochemical and molecular parameters in the serum and liver of high-fat diet-induced obese mice - Kai Lei; Ya-li Li; Yang Wang; Jing Wen; Hong-zhao Wu; Dong-you Yu; Wei-fen Li (Journal of Zhejiang University-SCIENCE B, 2015)

Pitavastatin calcium improves endothelial function and delays the progress of atherosclerosis in patients with hypercholesterolemia - Jing Zhao; Hui-min Yan; Ya Li; Jia Wang; Lu Han; Zhi-hao Wang; Meng-xiong Tang; Wei Zhang; Yun Zhang; Ming Zhong (Journal of Zhejiang University-SCIENCE B, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

miR-126 inhibits cell proliferation and induces cell apoptosis of hepatocellular carcinoma cells partially by targeting Sox2 - Chunfang Zhao; Ya Li; Ming Zhang; Yi Yang; Li Chang (Human Cell, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Tolerance and Antioxidant Response of a Dark Septate Endophyte (DSE), Exophiala pisciphila, to Cadmium Stress - Fangdong Zhan; Yongmei He; Tao Li; Yun-ya Yang; Gurpal S. Toor; Zhiwei Zhao (Bulletin of Environmental Contamination and Toxicology, 2015)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Simulation Model of Pyrolysis Biofuel Yield Based on Algal Components and Pyrolysis Kinetics - Xiaoyi Yang; Xin Wang; Bingwei Zhao; Ya Li (BioEnergy Research, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

RETRACTED ARTICLE: Genetic polymorphisms in the CYP1A1 and CYP1B1 genes and susceptibility to bladder cancer: a meta-analysis - Yan-Zhi Chen; Jing Li; Yu-Xia Zhao; Dan Liu; He-Tong Wang; Ya Gao; Ying Chen (Molecular Biology Reports, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Enhanced degradation of ortho-nitrochlorobenzene by the combined system of zero-valent iron reduction and persulfate oxidation in soils - Hai-bo Xu; Dao-yuan Zhao; Yu-jiao Li; Pei-ya Liu; Chang-xun Dong (Environmental Science and Pollution Research, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Functional study on the mutations in the silkworm (Bombyx mori) acetylcholinesterase type 1 gene (ace1) and its recombinant proteins - Ju-mei Wang; Bin-bin Wang; Yi Xie; Shan-shan Sun; Zhi-ya Gu; Lie Ma; Fan-chi Li; Yi-fan Zhao; Bin Yang; Wei-de Shen; Bing Li (Molecular Biology Reports, 2014)

Joint land-sea seismic survey and research on the deep structures of the Bohai Sea areas - Tianyao Hao; Qingyu You; Lihua Liu; Chuanchuan Lv; Ya Xu; Zhiwei Li; Chunlei Zhao; Yanpeng Zheng; Chenguang Liu; Guozhong Han (Acta Oceanologica Sinica, 2013)

MK-2206 induces cell cycle arrest and apoptosis in HepG2 cells and sensitizes TRAIL-mediated cell death - Peng Jiao; Yun-Sheng Zhou; Juan-Xia Yang; Ya-Li Zhao; Qiang-Qiang Liu; Chuang Yuan; Feng-Ze Wang (Molecular and Cellular Biochemistry, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Discrimination between Demodex folliculorum (Acari: Demodicidae) isolates from China and Spain based on mitochondrial cox1 sequences - Ya-e Zhao; Jun-xian Ma; Li Hu; Li-ping Wu; Manuel De Rojas (Journal of Zhejiang University-SCIENCE B, 2013)

Promoting role of an endophyte on the growth and contents of kinsenosides and flavonoids of Anoectochilus formosanus Hayata, a rare and threatened medicinal Orchidaceae plant - Fu-sheng Zhang; Ya-li Lv; Yue Zhao; Shun-xing Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of perfluorooctanesulfonate and perfluorobutanesulfonate on the growth and sexual development of Xenopus laevis - Qin-Qin Lou; Yin-Feng Zhang; Zhen Zhou; Ya-Li Shi; Ya-Nan Ge; Dong-Kai Ren; Hai-Ming Xu; Ya-Xian Zhao; Wu-Ji Wei; Zhan-Fen Qin (Ecotoxicology, 2013)

Induction of viable gynogenetic progeny using eggs and UV-irradiated sperm from the Chinese tetraploid loach, Misgurnus anguillicaudatus - Ya-Juan Li; Zhuo Yu; Ming-Zhao Zhang; Cong Qian; Syuiti Abe; Katsutoshi Arai (Aquaculture International, 2013)

New megastigmane glycoside and alkaloids from Streptomyces sp. YIM 63342 - Xue-Qiong Yang; Ya-Bin Yang; Hao Zhou; Guang-Wei He; Li-Xing Zhao; Li-Hua Xu; Zhong-Tao Ding (Natural Product Research, 2013)

A New Pyrazoline-Based Fluorescent Probe for Cu2+ in Live Cells - Meng-Meng Li; Shu-Ya Huang; Hui Ye; Fei Ge; Jun-Ying Miao; Bao-Xiang Zhao (Journal of Fluorescence, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Immune responses induced in HHD mice by multiepitope HIV vaccine based on cryptic epitope modification - Yinghui Li; Yuxiao Huang; Jiao Liang; Zhikai Xu; Yan Shen; Ning Zhang; Zhongxiang Liu; Ya Zhao (Molecular Biology Reports, 2013)

Control of postharvest soft rot caused by Erwinia carotovora of vegetables by a strain of Bacillus amyloliquefaciens and its potential modes of action - Yancun Zhao; Pengxia Li; Kaihong Huang; Yuning Wang; Huali Hu; Ya Sun (World Journal of Microbiology and Biotechnology, 2013)

Disruption of the transcription factor RBP-J results in osteopenia attributable to attenuated osteoclast differentiation - Jing Ma; Ya-Li Liu; Yi-Yang Hu; Ya-Ning Wei; Xing-Cheng Zhao; Guang-Ying Dong; Hong-Yan Qin; Yin Ding; Hua Han (Molecular Biology Reports, 2013)

Analyzing the promoters of two CYP9A genes in the silkworm Bombyx mori by dual-luciferase reporter assay - Si-Si Zhao; Guo-Dong Zhao; Tian-Yuan Di; Hua Ding; Xiao-Ling Wan; Bing Li; Yu-Hua Chen; Ya-Xiang Xu; Wei-De Shen; Zheng-Guo Wei (Molecular Biology Reports, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

3-Nitro-naphthalimide and nitrogen mustard conjugate NNM-25 induces hepatocellular carcinoma apoptosis via PARP-1/p53 pathway - Song-qiang Xie; Ya-hong Zhang; Qian Li; Feng-hua Xu; Jiu-wang Miao; Jin Zhao; Chao-jie Wang (Apoptosis, 2012)

PDTC attenuate LPS-induced kidney injury in systemic lupus erythematosus-prone MRL/lpr Mice - Jin-Xia Zhai; Zhao-Xiang Zhang; Ya-Juan Feng; Shu-Shu Ding; Xing-Hua Wang; Li-Wei Zou; Dong-Qing Ye (Molecular Biology Reports, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

An antifungal compound from Trichoderma harzianum SQR-T037 effectively controls Fusarium wilt of cucumber in continuously cropped soil - Li-Hua Chen; Ya-Qing Cui; Xing-Ming Yang; Di-Kun Zhao; Qi-Rong Shen (Australasian Plant Pathology, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

A meta-analysis of association between acne vulgaris and Demodex infestation - Ya-e Zhao; Li Hu; Li-ping Wu; Jun-xian Ma (Journal of Zhejiang University-SCIENCE B, 2012)

Two new xanthones from the pericarp of Garcinia mangostana - Yan Zhao; Jin-Ping Liu; Dan Lu; Ping-Ya Li; Lian-Xue Zhang (Natural Product Research, 2012)

Analysis of Lanthanide-Induced Conformational Change of the C-Terminal Domain on Centrin - Ya-Qin Zhao; Jun Yan; Li Song; Ya-Nan Feng; Ai-Hua Liang; Bin-Sheng Yang (Journal of Fluorescence, 2012)

Removal of genotoxicity in chlorinated secondary effluent of a domestic wastewater treatment plant during dechlorination - Qian-Yuan Wu; Yi Li; Hong-Ying Hu; Ya-Nan Ding; Huang Huang; Feng-Yun Zhao (Environmental Science and Pollution Research, 2012)

Facial dermatosis associated with Demodex: a case-control study - Ya-e Zhao; Yan Peng; Xiang-lan Wang; Li-ping Wu; Mei Wang; Hu-ling Yan; Sheng-xiang Xiao (Journal of Zhejiang University-SCIENCE B, 2011)

Influence of temperature and medium on viability of Demodex folliculorum and Demodex brevis (Acari: Demodicidae) - Ya-E Zhao; Na Guo; Li-Ping Wu (Experimental and Applied Acarology, 2011)

Profile of Organochlorine Pesticides in Soil Cores from Some Hotspot Areas of Beijing, China - Hang-Xin Cheng; Xing-Hong Li; Ya-Ping Wang; Chuan-Dong Zhao; Ying-Han Liu; Hong-Han Chen; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2011)

The origin of natural tetraploid loach Misgurnus anguillicaudatus (Teleostei: Cobitidae) inferred from meiotic chromosome configurations - Ya-Juan Li; Zhuo Yu; Ming-Zhao Zhang; Cong Qian; Syuiti Abe; Katsutoshi Arai (Genetica, 2011)

RETRACTED ARTICLE: NPC-16, a novel naphthalimide–polyamine conjugate, induced apoptosis and autophagy in human hepatoma HepG2 cells and Bel-7402 cells - Song-qiang Xie; Qian Li; Ya-hong Zhang; Jian-hong Wang; Zi-hou Mei; Jin Zhao; Chao-jie Wang (Apoptosis, 2011)

Chromosome banding and FISH with rDNA probe in the diploid and tetraploid loach Misgurnus anguillicaudatus - Ya-Juan Li; Yi Tian; Ming-Zhao Zhang; Ping-Ping Tian; Zhuo Yu; Syuiti Abe; Katsutoshi Arai (Ichthyological Research, 2010)

A new antioxidant xanthone from the pericarp of Garcinia mangostana Linn. - Yan Zhao; Jin-Ping Liu; Dan Lu; Ping-Ya Li; Lian-Xue Zhang (Natural Product Research, 2010)

A new 3,4-seco-lupane-type triterpenoid from the pulp of Acanthopanax senticosus (Rupr. et Maxim) Harms - Zhao-Wei Yan; Jin-Ping Liu; Dan Lu; Paul Groundwater; Chun-Yan He; Ping-Ya Li (Natural Product Research, 2010)

Post-conditioning protects cardiomyocytes from apoptosis via PKCε-interacting with calcium-sensing receptors to inhibit endo(sarco)plasmic reticulum–mitochondria crosstalk - Shiyun Dong; Zongyan Teng; Fang-hao Lu; Ya-jun Zhao; Hulun Li; Huan Ren; He Chen; Zhen-wei Pan; Yan-jie Lv; Bao-feng Yang; Ye Tian; Chang-qing Xu; et al. (Molecular and Cellular Biochemistry, 2010)

Arsenic trioxide induces the apoptosis in vascular smooth muscle cells via increasing intracellular calcium and ROS formation - Jing-Xiu Li; Ya-Qi Shen; Ben-Zhi Cai; Jing Zhao; Xiaopeng Bai; Yan-Jie Lu; Xue-Qi Li (Molecular Biology Reports, 2010)

A novel polymorphism of GDF5 gene and its association with body measurement traits in Bos taurus and Bos indicus breeds - Yong Feng Liu; Lin Sen Zan; Kui Li; Shuan Ping Zhao; Ya Ping Xin; Qing Lin; Wan Qiang Tian; Zhi Wei Wang (Molecular Biology Reports, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Effects of Gestational Cadmium Exposure on Pregnancy Outcome and Development in the Offspring at Age 4.5 Years - Li-Li Tian; Yong-Cheng Zhao; Xiao-Chun Wang; Jin-Long Gu; Zhi-Juan Sun; Ya-Li Zhang; Ji-Xian Wang (Biological Trace Element Research, 2009)

A new bile acid from the bile of Anser anser - Zhao-Wei Yan; Jin-Ping Liu; Dan Lu; Jian-Fei Xue; Ping-Ya Li (Natural Product Research, 2009)

Activation of Group III Metabotropic Glutamate Receptor Reduces Intracellular Calcium in β-Amyloid Peptide [31–35]-Treated Cortical Neurons - Li Zhao; Shen Ting Zhao; Zhong Ming Qian; Ce Zhang; Xiao Mei Wu; Fang Du; Ya Ke (Neurotoxicity Research, 2009)

Adenovirus-mediated PDCD5 gene transfer sensitizes K562 cells to apoptosis induced by idarubicin in vitro and in vivo - Guo-Rui Ruan; Hong-Shan Zhao; Yan Chang; Jin-Lan Li; Ya-Zhen Qin; Yan-Rong Liu; Shan-Shan Chen; Xiao-Jun Huang (Apoptosis, 2008)

Localization of a novel gene for congenital nonsyndromic simple microphthalmia to chromosome 2q11-14 - Hui Li; Jia-Xin Wang; Cheng-Ye Wang; Ping Yu; Qiang Zhou; Yong-Gang Chen; Lu-Hang Zhao; Ya-Ping Zhang (Human Genetics, 2008)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Enhancing antioxidative capacity of Lepidium meyenii calli by addition of methyl salicylate to culture medium - Ya-Li Wang; Xiao-Dong Wang; Bing Zhao; Yu-Chun Wang (Acta Physiologiae Plantarum, 2007)

A novel cycloartane triterpene glycoside from the seeds of Cassia sophera L. - Yan Zhao; Jin-Ping Liu; Dan Lu; Ping-Ya Li (Natural Product Research, 2007)

Isolation, Characterization and Phylogenetic Analysis of an Aerobic Bacterium Capable of Degrading Bensulfuronmethyl - Ya-Wei Zhu; Yu-Hua Zhao; Xiao-Yan Lin; Li Yang (World Journal of Microbiology and Biotechnology, 2005)

Pedoecological effects of a sand-fixing poplar (Populus simonii Carr.) forest in a desertified sandy land of Inner Mongolia, China - Feng-Rui Li; Hua Zhang; Li-Ya Zhao; Yasuhito Shirato; Xian-Zhi Wang (Plant and Soil, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)